Plant size, latitude, and phylogeny explain within-population variability in herbivory - Robinson, M. L.; Hahn, P. G.; Inouye, B. D.; Underwood, N.; Whitehead, S. R.; Abbott, K. C.; Bruna, E. M.; Cacho, N. I.; Dyer, L. A.; Abdala-Roberts, L.; Allen, W. J.; Andrade, J. F.; et al. (Science)
Interactions between plants and herbivores are central in most ecosystems, but their strength is highly variable. The amount of variability within a system is thought to influence most aspects of plant-herbivore biology, from ecological stability to plant defense evolution. Our understanding of what influences variability, however, is limited by sparse data. We collected standardized surveys of herbivory for 503 plant species at 790 sites across 116° of latitude. With these data, we show that within-population variability in herbivory increases with latitude, decreases with plant size, and is phylogenetically structured. Differences in the magnitude of variability are thus central to how plant-herbivore biology varies across macroscale gradients. We argue that increased focus on interaction variability will advance understanding of patterns of life on Earth.

Millennia-long epigenetic fluctuations generate intragenic DNA methylation variance in Arabidopsis populations - Briffa, Amy; Hollwey, Elizabeth; Shahzad, Zaigham; Moore, Jonathan D.; Lyons, David B.; Howard, Martin; Zilberman, Daniel (Cell Systems)
Methylation of CG dinucleotides (mCGs), which regulates eukaryotic genome functions, is epigenetically propagated by Dnmt1/MET1 methyltransferases. How mCG is established and transmitted across generations despite imperfect enzyme fidelity is unclear. Whether mCG variation in natural populations is governed by genetic or epigenetic inheritance also remains mysterious. Here, we show that MET1 de novo activity, which is enhanced by existing proximate methylation, seeds and stabilizes mCG in Arabidopsis thaliana genes. MET1 activity is restricted by active demethylation and suppressed by histone variant H2A.Z, producing localized mCG patterns. Based on these observations, we develop a stochastic mathematical model that precisely recapitulates mCG inheritance dynamics and predicts intragenic mCG patterns and their population-scale variation given only CG site spacing. Our results demonstrate that intragenic mCG establishment, inheritance, and variance constitute a unified epigenetic process, revealing that intragenic mCG undergoes large, millennia-long epigenetic fluctuations and can therefore mediate evolution on this timescale.

HerbVar-Network/HV-Large-Patterns-MS-public: v1.0.0 - Wetzel, William
This is associated with our paper "Plant size, latitude, and phylogeny explain within-population variability in herbivory" published in Science.

ArpC5 isoforms regulate Arp2/3 complex–dependent protrusion through differential Ena/VASP positioning - Fäßler, Florian; Javoor, Manjunath; Datler, Julia; Döring, Hermann; Hofer, Florian; Dimchev, Georgi A; Hodirnau, Victor-Valentin; Faix, Jan; Rottner, Klemens; Schur, Florian KM (Science Advances)
Regulation of the Arp2/3 complex is required for productive nucleation of branched actin networks. An emerging aspect of regulation is the incorporation of subunit isoforms into the Arp2/3 complex. Specifically, both ArpC5 subunit isoforms, ArpC5 and ArpC5L, have been reported to fine-tune nucleation activity and branch junction stability. We have combined reverse genetics and cellular structural biology to describe how ArpC5 and ArpC5L differentially affect cell migration. Both define the structural stability of ArpC1 in branch junctions and, in turn, by determining protrusion characteristics, affect protein dynamics and actin network ultrastructure. ArpC5 isoforms also affect the positioning of members of the Ena/Vasodilator-stimulated phosphoprotein (VASP) family of actin filament elongators, which mediate ArpC5 isoform–specific effects on the actin assembly level. Our results suggest that ArpC5 and Ena/VASP proteins are part of a signaling pathway enhancing cell migration.
Keywords: Multidisciplinary

Research data of the publication "ArpC5 isoforms regulate Arp2/3 complex-dependent protrusion through differential Ena/VASP positioning" - Schur, Florian KM
Regulation of the Arp2/3 complex is required for productive nucleation of branched actin networks. An emerging aspect of regulation is the incorporation of subunit isoforms into the Arp2/3 complex. Specifically, both ArpC5 subunit isoforms, ArpC5 and ArpC5L, have been reported to fine-tune nucleation activity and branch junction stability. We have combined reverse genetics and cellular structural biology to describe how ArpC5 and ArpC5L differentially affect cell migration. Both define the structural stability of ArpC1 in branch junctions and, in turn, by determining protrusion characteristics, affect protein dynamics and actin network ultrastructure. ArpC5 isoforms also affect the positioning of members of the Ena/Vasodilator-stimulated phosphoprotein (VASP) family of actin filament elongators, which mediate ArpC5 isoform–specific effects on the actin assembly level. Our results suggest that ArpC5 and Ena/VASP proteins are part of a signaling pathway enhancing cell migration.

Computational toolbox for ultrastructural quantitative analysis of filament networks in cryo-ET data - Dimchev, Georgi A; Amiri, Behnam; Fäßler, Florian; Falcke, Martin; Schur, Florian KM
A precise quantitative description of the ultrastructural characteristics underlying biological mechanisms is often key to their understanding. This is particularly true for dynamic extra- and intracellular filamentous assemblies, playing a role in cell motility, cell integrity, cytokinesis, tissue formation and maintenance. For example, genetic manipulation or modulation of actin regulatory proteins frequently manifests in changes of the morphology, dynamics, and ultrastructural architecture of actin filament-rich cell peripheral structures, such as lamellipodia or filopodia. However, the observed ultrastructural effects often remain subtle and require sufficiently large datasets for appropriate quantitative analysis. The acquisition of such large datasets has been enabled by recent advances in high-throughput cryo-electron tomography (cryo-ET) methods. This also necessitates the development of complementary approaches to maximize the extraction of relevant biological information. We have developed a computational toolbox for the semi-automatic quantification of segmented and vectorized fila- mentous networks from pre-processed cryo-electron tomograms, facilitating the analysis and cross-comparison of multiple experimental conditions. GUI-based components simplify the processing of data and allow users to obtain a large number of ultrastructural parameters describing filamentous assemblies. We demonstrate the feasibility of this workflow by analyzing cryo-ET data of untreated and chemically perturbed branched actin filament networks and that of parallel actin filament arrays. In principle, the computational toolbox presented here is applicable for data analysis comprising any type of filaments in regular (i.e. parallel) or random arrangement. We show that it can ease the identification of key differences between experimental groups and facilitate the in-depth analysis of ultrastructural data in a time-efficient manner.
Keywords: cryo-electron tomography; actin cytoskeleton; toolbox

Adaptive pathfinding by nucleokinesis during amoeboid migration - Kroll, Janina; Hauschild, Robert; Kuznetcov, Arthur; Stefanowski, Kasia; Hermann, Monika D.; Merrin, Jack; Shafeek, Lubuna B; Müller-Taubenberger, Annette; Renkawitz, Jörg (EMBO Journal)
Motile cells moving in multicellular organisms encounter microenvironments of locally heterogeneous mechanochemical composition. Individual compositional parameters like chemotactic signals, adhesiveness, and pore sizes are well known to be sensed by motile cells, providing individual guidance cues for cellular pathfinding. However, motile cells encounter diverse mechanochemical signals at the same time, raising the question of how cells respond to locally diverse and potentially competing signals on their migration routes. Here, we reveal that motile amoeboid cells require nuclear repositioning, termed nucleokinesis, for adaptive pathfinding in heterogeneous mechanochemical microenvironments. Using mammalian immune cells and the amoeba Dictyostelium discoideum , we discover that frequent, rapid and long-distance nucleokinesis is a basic component of amoeboid pathfinding, enabling cells to reorientate quickly between locally competing cues. Amoeboid nucleokinesis comprises a two-step cell polarity switch and is driven by myosin II-forces, sliding the nucleus from a ‘losing’ to the ‘winning’ leading edge to re-adjust the nuclear to the cellular path. Impaired nucleokinesis distorts fast path adaptions and causes cellular arrest in the microenvironment. Our findings establish that nucleokinesis is required for amoeboid cell navigation. Given that motile single-cell amoebae, many immune cells, and some cancer cells utilize an amoeboid migration strategy, these results suggest that amoeboid nucleokinesis underlies cellular navigation during unicellular biology, immunity, and disease.

Stress granules plug and stabilize damaged endolysosomal membranes - Bussi, Claudio; Mangiarotti, Agustín; Vanhille-Campos, Christian Eduardo; Aylan, Beren; Pellegrino, Enrica; Athanasiadi, Natalia; Fearns, Antony; Rodgers, Angela; Franzmann, Titus M.; Šarić, Anđela; Dimova, Rumiana; Gutierrez, Maximiliano G. (Nature)
Abstract Endomembrane damage represents a form of stress that is detrimental for eukaryotic cells 1,2 . To cope with this threat, cells possess mechanisms that repair the damage and restore cellular homeostasis 3–7 . Endomembrane damage also results in organelle instability and the mechanisms by which cells stabilize damaged endomembranes to enable membrane repair remains unknown. Here, by combining in vitro and in cellulo studies with computational modelling we uncover a biological function for stress granules whereby these biomolecular condensates form rapidly at endomembrane damage sites and act as a plug that stabilizes the ruptured membrane. Functionally, we demonstrate that stress granule formation and membrane stabilization enable efficient repair of damaged endolysosomes, through both ESCRT (endosomal sorting complex required for transport)-dependent and independent mechanisms. We also show that blocking stress granule formation in human macrophages creates a permissive environment for Mycobacterium tuberculosis , a human pathogen that exploits endomembrane damage to survive within the host.
Keywords: Multidisciplinary

Stress granules plug and stabilize damaged endolysosomal membranes - Vanhille-Campos, Christian Eduardo; Šarić, Anđela
Data related to the following paper: "Stress granules plug and stabilize damaged endolysosomal membranes" (https://doi.org/10.1038/s41586-023-06726-w) Abstract: Endomembrane damage represents a form of stress that is detrimental for eukaryotic cells. To cope with this threat, cells possess mechanisms that repair the damage and restore cellular homeostasis. Endomembrane damage also results in organelle instability and the mechanisms by which cells stabilize damaged endomembranes to enable membrane repair remains unknown. In this work we use a minimal coarse-grained molecular dynamics system to explore how lipid vesicles undergoing poration in a protein-rich medium can be plugged and stabilised by condensate formation. The solution of proteins in and out of the vesicle is described by beads dispersed in implicit solvent. The membrane is described as a one-bead-thick fluid elastic layer of mechanical properties that mimic biological membranes. We tune the interactions between solution beads in the different compartments to capture the differences between the cytoplasmic and endosomal protein solutions and explore how the system responds to different degrees of membrane poration. We find that, in the right interaction regime, condensates form rapidly at the damage site upon solution mixing and act as a plug that prevents futher mixing and destabilisation of the vesicle. Further, when the condensate can interact with the membrane (wetting interactions) we find that it mediates pore sealing and membrane repair. This research is part of the work published in "Stress granules plug and stabilize damaged endolysosomal membranes", Bussi et al, Nature, 2023 - 10.1038/s41586-023-06726-w.

PCYT2-regulated lipid biosynthesis is critical to muscle health and ageing - Cikes, Domagoj; Elsayad, Kareem; Sezgin, Erdinc; Koitai, Erika; Ferenc, Torma; Orthofer, Michael; Yarwood, Rebecca; Heinz, Leonhard X.; Sedlyarov, Vitaly; Darwish-Miranda, Nasser; Taylor, Adrian; Grapentine, Sophie; et al. (Nature Metabolism)
Muscle degeneration is the most prevalent cause for frailty and dependency in inherited diseases and ageing. Elucidation of pathophysiological mechanisms, as well as effective treatments for muscle diseases, represents an important goal in improving human health. Here, we show that the lipid synthesis enzyme phosphatidylethanolamine cytidyltransferase (PCYT2/ECT) is critical to muscle health. Human deficiency in PCYT2 causes a severe disease with failure to thrive and progressive weakness. pcyt2-mutant zebrafish and muscle-specific Pcyt2-knockout mice recapitulate the participant phenotypes, with failure to thrive, progressive muscle weakness and accelerated ageing. Mechanistically, muscle Pcyt2 deficiency affects cellular bioenergetics and membrane lipid bilayer structure and stability. PCYT2 activity declines in ageing muscles of mice and humans, and adeno-associated virus-based delivery of PCYT2 ameliorates muscle weakness in Pcyt2-knockout and old mice, offering a therapy for individuals with a rare disease and muscle ageing. Thus, PCYT2 plays a fundamental and conserved role in vertebrate muscle health, linking PCYT2 and PCYT2-synthesized lipids to severe muscle dystrophy and ageing.
Keywords: Cell Biology; Physiology (medical); Endocrinology; Diabetes and Metabolism; Internal Medicine

Role of high-order lattice anharmonicity in the phonon thermal transport of silver halide AgX (X=Cl,Br, I) - Ouyang, Niuchang; Zeng, Zezhu; Wang, Chen; Wang, Qi; Chen, Yue (Physical Review B)
The phonon transport mechanisms and ultralow lattice thermal conductivities (κL) in silver halide AgX (X=Cl,Br,I) compounds are not yet well understood. Herein, we study the lattice dynamics and thermal property of AgX under the framework of perturbation theory and the two-channel Wigner thermal transport model based on accurate machine learning potentials. We find that an accurate extraction of the third-order atomic force constants from largely displaced configurations is significant for the calculation of the κL of AgX, and the coherence thermal transport is also non-negligible. In AgI, however, the calculated κL still considerably overestimates the experimental values even including four-phonon scatterings. Molecular dynamics (MD) simulations using machine learning potential suggest an important role of the higher-than-fourth-order lattice anharmonicity in the low-frequency phonon linewidths of AgI at room temperature, which can be related to the simultaneous restrictions of the three- and four-phonon phase spaces. The κL of AgI calculated using MD phonon lifetimes including full-order lattice anharmonicity shows a better agreement with experiments.

Practical asynchronous high-threshold distributed key generation and distributed polynomial sampling - Das, Sourav; Xiang, Zhuolun; Kokoris Kogias, Eleftherios; Ren, Ling (32nd USENIX Security Symposium)
Distributed Key Generation (DKG) is a technique to bootstrap threshold cryptosystems without a trusted party. DKG is an essential building block to many decentralized protocols such as randomness beacons, threshold signatures, Byzantine consensus, and multiparty computation. While significant progress has been made recently, existing asynchronous DKG constructions are inefficient when the reconstruction threshold is larger than one-third of the total nodes. In this paper, we present a simple and concretely efficient asynchronous DKG (ADKG) protocol among n = 3t + 1 nodes that can tolerate up to t malicious nodes and support any reconstruction threshold ℓ ≥ t. Our protocol has an expected O(κn3) communication cost, where κ is the security parameter, and only assumes the hardness of the Discrete Logarithm. The core ingredient of our ADKG protocol is an asynchronous protocol to secret share a random polynomial of degree ℓ ≥ t, which has other applications, such as asynchronous proactive secret sharing and asynchronous multiparty computation. We implement our high-threshold ADKG protocol and evaluate it using a network of up to 128 geographically distributed nodes. Our evaluation shows that our high-threshold ADKG protocol reduces the running time by 90% and bandwidth usage by 80% over the state-of-the-art.

A streamlined molecular-dynamics workflow for computing solubilities of molecular and ionic crystals - Reinhardt, Aleks; Chew, Pin Yu; Cheng, Bingqing (Journal of Chemical Physics)
Computing the solubility of crystals in a solvent using atomistic simulations is notoriously challenging due to the complexities and convergence issues associated with free-energy methods, as well as the slow equilibration in direct-coexistence simulations. This paper introduces a molecular-dynamics workflow that simplifies and robustly computes the solubility of molecular or ionic crystals. This method is considerably more straightforward than the state-of-the-art, as we have streamlined and optimised each step of the process. Specifically, we calculate the chemical potential of the crystal using the gas-phase molecule as a reference state, and employ the S0 method to determine the concentration dependence of the chemical potential of the solute. We use this workflow to predict the solubilities of sodium chloride in water, urea polymorphs in water, and paracetamol polymorphs in both water and ethanol. Our findings indicate that the predicted solubility is sensitive to the chosen potential energy surface. Furthermore, we note that the harmonic approximation often fails for both molecular crystals and gas molecules at or above room temperature, and that the assumption of an ideal solution becomes less valid for highly soluble substances.

The X chromosome of insects likely predates the origin of class Insecta - Toups, Melissa A; Vicoso, Beatriz (Evolution)
Sex chromosomes have evolved independently multiple times, but why some are conserved for more than 100 million years whereas others turnover rapidly remains an open question. Here, we examine the homology of sex chromosomes across nine orders of insects, plus the outgroup springtails. We find that the X chromosome is likely homologous across insects and springtails; the only exception is in the Lepidoptera, which has lost the X and now has a ZZ/ZW sex-chromosome system. These results suggest the ancestral insect X chromosome has persisted for more than 450 million years—the oldest known sex chromosome to date. Further, we propose that the shrinking of gene content the dipteran X chromosome has allowed for a burst of sex-chromosome turnover that is absent from other speciose insect orders.

The X chromosome of insects likely predates the origin of Class Insecta - Toups, Melissa A; Vicoso, Beatriz
Sex chromosomes have evolved independently multiple times, but why some are conserved for more than 100 million years whereas others turnover rapidly remains an open question. Here, we examine the homology of sex chromosomes across nine orders of insects, plus the outgroup springtails. We find that the X chromosome is likely homologous across insects and springtails; the only exception is in the Lepidoptera, which has lost the X and now has a ZZ/ZW sex chromosome system. These results suggest the ancestral insect X chromosome has persisted for more than 450 million years – the oldest known sex chromosome to date. Further, we propose that the shrinking of gene content of the Dipteran X chromosome has allowed for a burst of sex-chromosome turnover that is absent from other speciose insect orders.

The X chromosome of insects likely predates the origin of Class Insecta - Toups, Melissa A; Vicoso, Beatriz
Sex chromosomes have evolved independently multiple times, but why some are conserved for more than 100 million years whereas others turnover rapidly remains an open question. Here, we examine the homology of sex chromosomes across nine orders of insects, plus the outgroup springtails. We find that the X chromosome is likely homologous across insects and springtails; the only exception is in the Lepidoptera, which has lost the X and now has a ZZ/ZW sex chromosome system. These results suggest the ancestral insect X chromosome has persisted for more than 450 million years – the oldest known sex chromosome to date. Further, we propose that the shrinking of gene content of the Dipteran X chromosome has allowed for a burst of sex-chromosome turnover that is absent from other speciose insect orders.

BingqingCheng/solubility: V1.0 - Cheng, Bingqing
Data underlying the publication "A streamlined molecular-dynamics workflow for computing solubilities of molecular and ionic crystals" (DOI https://doi.org/10.1063/5.0173341).

A shallow‐deep unified stochastic mass flux cumulus parameterization in the single column community climate model - Khouider, B.; GOSWAMI, BIDYUT B; Phani, R.; Majda, A. J. (Journal of Advances in Modeling Earth Systems)
Cumulus parameterization (CP) in state‐of‐the‐art global climate models is based on the quasi‐equilibrium assumption (QEA), which views convection as the action of an ensemble of cumulus clouds, in a state of equilibrium with respect to a slowly varying atmospheric state. This view is not compatible with the organization and dynamical interactions across multiple scales of cloud systems in the tropics and progress in this research area was slow over decades despite the widely recognized major shortcomings. Novel ideas on how to represent key physical processes of moist convection‐large‐scale interaction to overcome the QEA have surged recently. The stochastic multicloud model (SMCM) CP in particular mimics the dynamical interactions of multiple cloud types that characterize organized tropical convection. Here, the SMCM is used to modify the Zhang‐McFarlane (ZM) CP by changing the way in which the bulk mass flux and bulk entrainment and detrainment rates are calculated. This is done by introducing a stochastic ensemble of plumes characterized by randomly varying detrainment level distributions based on the cloud area fraction of the SMCM. The SMCM is here extended to include shallow cumulus clouds resulting in a unified shallow‐deep CP. The new stochastic multicloud plume CP is validated against the control ZM scheme in the context of the single column Community Climate Model of the National Center for Atmospheric Research using data from both tropical ocean and midlatitude land convection. Some key features of the SMCM CP such as it capability to represent the tri‐modal nature of organized convection are emphasized.
Keywords: General Earth and Planetary Sciences; Environmental Chemistry; Global and Planetary Change

Accurate determination of the shapes of granular charge distributions - Mujica, Nicolás; Waitukaitis, Scott R (Physical Review E)
Experiments have shown that charge distributions of granular materials are non-Gaussian, with broad tails that indicate many particles with high charge. This observation has consequences for the behavior of granular materials in many settings, and may bear relevance to the underlying charge transfer mechanism. However, there is the unaddressed possibility that broad tails arise due to experimental uncertainties, as determining the shapes of tails is nontrivial. Here we show that measurement uncertainties can indeed account for most of the tail broadening previously observed. The clue that reveals this is that distributions are sensitive to the electric field at which they are measured; ones measured at low (high) fields have larger (smaller) tails. Accounting for sources of uncertainty, we reproduce this broadening in silico. Finally, we use our results to back out the true charge distribution without broadening, which we find is still non-Guassian, though with substantially different behavior at the tails and indicating significantly fewer highly charged particles. These results have implications in many natural settings where electrostatic interactions, especially among highly charged particles, strongly affect granular behavior.

Weighted packet selection for rechargeable links in cryptocurrency networks: Complexity and approximation - Schmid, Stefan; Svoboda, Jakub; Yeo, Michelle X (SIROCCO 2023: Structural Information and Communication Complexity)
We consider a natural problem dealing with weighted packet selection across a rechargeable link, which e.g., finds applications in cryptocurrency networks. The capacity of a link (u, v) is determined by how much nodes u and v allocate for this link. Specifically, the input is a finite ordered sequence of packets that arrive in both directions along a link. Given (u, v) and a packet of weight x going from u to v, node u can either accept or reject the packet. If u accepts the packet, the capacity on link (u, v) decreases by x. Correspondingly, v’s capacity on (u, v) increases by x. If a node rejects the packet, this will entail a cost affinely linear in the weight of the packet. A link is “rechargeable” in the sense that the total capacity of the link has to remain constant, but the allocation of capacity at the ends of the link can depend arbitrarily on the nodes’ decisions. The goal is to minimise the sum of the capacity injected into the link and the cost of rejecting packets. We show that the problem is NP-hard, but can be approximated efficiently with a ratio of (1+ε)⋅(1+3–√) for some arbitrary ε>0. .

Advances in efficiency and privacy in payment channel network analysis - Yeo, Michelle X
Payment channel networks are a promising approach to improve the scalability bottleneck of cryptocurrencies. Two design principles behind payment channel networks are efficiency and privacy. Payment channel networks improve efficiency by allowing users to transact in a peer-to-peer fashion along multi-hop routes in the network, avoiding the lengthy process of consensus on the blockchain. Transacting over payment channel networks also improves privacy as these transactions are not broadcast to the blockchain. Despite the influx of recent protocols built on top of payment channel networks and their analysis, a common shortcoming of many of these protocols is that they typically focus only on either improving efficiency or privacy, but not both. Another limitation on the efficiency front is that the models used to model actions, costs and utilities of users are limited or come with unrealistic assumptions. This thesis aims to address some of the shortcomings of recent protocols and algorithms on payment channel networks, particularly in their privacy and efficiency aspects. We first present a payment route discovery protocol based on hub labelling and private information retrieval that hides the route query and is also efficient. We then present a rebalancing protocol that formulates the rebalancing problem as a linear program and solves the linear program using multiparty computation so as to hide the channel balances. The rebalancing solution as output by our protocol is also globally optimal. We go on to develop more realistic models of the action space, costs, and utilities of both existing and new users that want to join the network. In each of these settings, we also develop algorithms to optimise the utility of these users with good guarantees on the approximation and competitive ratios.

Lightning creation games - Avarikioti, Zeta; Lizurej, Tomasz; Michalak, Tomasz; Yeo, Michelle X (43rd International Conference on Distributed Computing Systems)
Payment channel networks (PCNs) are a promising solution to the scalability problem of cryptocurrencies. Any two users connected by a payment channel in the network can theoretically send an unbounded number of instant, costless transactions between them. Users who are not directly connected can also transact with each other in a multi-hop fashion. In this work, we study the incentive structure behind the creation of payment channel networks, particularly from the point of view of a single user that wants to join the network. We define a utility function for a new user in terms of expected revenue, expected fees, and the cost of creating channels, and then provide constant factor approximation algorithms that optimise the utility function given a certain budget. Additionally, we take a step back from a single user to the whole network and examine the parameter spaces under which simple graph topologies form a Nash equilibrium.

Synchronization in collectively moving active matter - Riedl, Michael
Most motions of many-body systems at any scale in nature with sufficient degrees of freedom tend to be chaotic; reaching from the orbital motion of planets, the air currents in our atmosphere, down to the water flowing through our pipelines or the movement of a population of bacteria. To the observer it is therefore intriguing when a moving collective exhibits order. Collective motion of flocks of birds, schools of fish or swarms of self-propelled particles or robots have been studied extensively over the past decades but the mechanisms involved in the transition from chaos to order remain unclear. Here, the interactions, that in most systems give rise to chaos, sustain order. In this thesis we investigate mechanisms that preserve, destabilize or lead to the ordered state. We show that endothelial cells migrating in circular confinements transition to a collective rotating state and concomitantly synchronize the frequencies of nucleating actin waves within individual cells. Consequently, the frequency dependent cell migration speed uniformizes across the population. Complementary to the WAVE dependent nucleation of traveling actin waves, we show that in leukocytes the actin polymerization depending on WASp generates pushing forces locally at stationary patches. Next, in pipe flows, we study methods to disrupt the self–sustaining cycle of turbulence and therefore relaminarize the flow. While we find in pulsating flow conditions that turbulence emerges through a helical instability during the decelerating phase. Finally, we show quantitatively in brain slices of mice that wild-type control neurons can compensate the migratory deficits of a genetically modified neuronal sub–population in the developing cortex.

Synchronization in collectively moving active matter - Riedl, Michael
Most motions of many-body systems at any scale in nature with sufficient degrees of freedom tend to be chaotic; reaching from the orbital motion of planets, the air currents in our atmosphere, down to the water flowing through our pipelines or the movement of a population of bacteria. To the observer it is therefore intriguing when a moving collective exhibits order. Collective motion of flocks of birds, schools of fish or swarms of self-propelled particles or robots have been studied extensively over the past decades but the mechanisms involved in the transition from chaos to order remain unclear. Here, the interactions, that in most systems give rise to chaos, sustain order. In this thesis we investigate mechanisms that preserve, destabilize or lead to the ordered state. We show that endothelial cells migrating in circular confinements transition to a collective rotating state and concomitantly synchronize the frequencies of nucleating actin waves within individual cells. Consequently, the frequency dependent cell migration speed uniformizes across the population. Complementary to the WAVE dependent nucleation of traveling actin waves, we show that in leukocytes the actin polymerization depending on WASp generates pushing forces locally at stationary patches. Next, in pipe flows, we study methods to disrupt the self--sustaining cycle of turbulence and therefore relaminarize the flow. While we find in pulsating flow conditions that turbulence emerges through a helical instability during the decelerating phase. Finally, we show quantitatively in brain slices of mice that wild-type control neurons can compensate the migratory deficits of a genetically modified neuronal sub--population in the developing cortex.
Keywords: Synchronization; Collective Movement; Active Matter; Cell Migration; Active Colloids

Resonant microwave spectroscopy of Al-InAs - Phan, Duc T
Superconductor-semiconductor heterostructures currently capture a significant amount of research interest and they serve as the physical platform in many proposals towards topological quantum computation. Despite being under extensive investigations, historically using transport techniques, the basic properties of the interface between the superconductor and the semiconductor remain to be understood. In this thesis, two separate studies on the Al-InAs heterostructures are reported with the first focusing on the physics of the material motivated by the emergence of a new phase, the Bogoliubov-Fermi surface. The second focuses on a technological application, a gate-tunable Josephson parametric amplifier. In the first study, we investigate the hypothesized unconventional nature of the induced superconductivity at the interface between the Al thin film and the InAs quantum well. We embed a two-dimensional Al-InAs hybrid system in a resonant microwave circuit allowing measurements of change in inductance. The behaviour of the resonance in a range of temperature and in-plane magnetic field has been studied and compared with the theory of conventional s-wave superconductor and a two-component theory that includes both contribution of the $s$-wave pairing in Al and the intraband $p ± ip$ pairing in InAs. Measuring the temperature dependence of resonant frequency, no discrepancy is found between data and the conventional theory. We observe the breakdown of superconductivity due to an applied magnetic field which contradicts the conventional theory. In contrast, the data can be captured quantitatively by fitting to a two-component model. We find the evidence of the intraband $p ± ip$ pairing in the InAs and the emergence of the Bogoliubov-Fermi surfaces due to magnetic field with the characteristic value $B^* = 0.33~T$. From the fits, the sheet resistance of Al, the carrier density and mobility in InAs are determined. By systematically studying the anisotropy of the circuit response, we find weak anisotropy for $B < B^*$ and increasingly strong anisotropy for $B > B^*$ resulting in a pronounced two-lobe structure in polar plot of frequency versus field angle. Strong resemblance between the field dependence of dissipation and superfluid density hints at a hidden signature of the Bogoliubov-Fermi surface that is burried in the dissipation data. In the second study, we realize a parametric amplifier with a Josephson field effect transistor as the active element. The device's modest construction consists of a gated SNS weak link embedded at the center of a coplanar waveguide resonator. By applying a gate voltage, the resonant frequency is field-effect tunable over a range of 2 GHz. Modelling the JoFET minimally as a parallel RL circuit, the dissipation introduced by the JoFET can be quantitatively related to the gate voltage. We observed gate-tunable Kerr nonlinearity qualitatively in line with expectation. The JoFET amplifier has 20 dB of gain, 4 MHz of instantaneous bandwidth, and a 1dB compression point of -125.5 dBm when operated at a fixed resonant frequency. In general, the signal-to-noise ratio is improved by 5-7 dB when the JoFET amplifier is activated compared. The noise of the measurement chain and insertion loss of relevant circuit elements are calibrated to determine the expected and the real noise performance of the JoFET amplifier. As a quantification of the noise performance, the measured total input-referred noise of the JoFET amplifier is in good agreement with the estimated expectation which takes device loss into account. We found that the noise performance of the device reported in this document approaches one photon of total input-referred added noise which is the quantum limit imposed in nondegenerate parametric amplifier.
Keywords: superconductor-semiconductor; superconductivity; Al; InAs; p-wave; superconductivity; JPA; microwave

Gate-tunable superconductor-semiconductor parametric amplifier - Phan, Duc T; Falthansl-Scheinecker, Paul; Mishra, Umang; Strickland, W. M.; Langone, D.; Shabani, J.; Higginbotham, Andrew P (Physical Review Applied)
We build a parametric amplifier with a Josephson field-effect transistor (JoFET) as the active element. The resonant frequency of the device is field-effect tunable over a range of 2 GHz. The JoFET amplifier has 20 dB of gain, 4 MHz of instantaneous bandwidth, and a 1-dB compression point of -125.5 dBm when operated at a fixed resonance frequency.

Procedural metamaterials: A unified procedural graph for metamaterial design - Makatura, Liane; Wang, Bohan; Chen, Yi-Lu; Deng, Bolei; Wojtan, Christopher J; Bickel, Bernd; Matusik, Wojciech (ACM Transactions on Graphics)
We introduce a compact, intuitive procedural graph representation for cellular metamaterials, which are small-scale, tileable structures that can be architected to exhibit many useful material properties. Because the structures’ “architectures” vary widely—with elements such as beams, thin shells, and solid bulks—it is difficult to explore them using existing representations. Generic approaches like voxel grids are versatile, but it is cumbersome to represent and edit individual structures; architecture-specific approaches address these issues, but are incompatible with one another. By contrast, our procedural graph succinctly represents the construction process for any structure using a simple skeleton annotated with spatially varying thickness. To express the highly constrained triply periodic minimal surfaces (TPMS) in this manner, we present the first fully automated version of the conjugate surface construction method, which allows novices to create complex TPMS from intuitive input. We demonstrate our representation’s expressiveness, accuracy, and compactness by constructing a wide range of established structures and hundreds of novel structures with diverse architectures and material properties. We also conduct a user study to verify our representation’s ease-of-use and ability to expand engineers’ capacity for exploration.
Keywords: Computer Graphics and Computer-Aided Design

Mechanism of mammalian transcriptional repression by noncoding RNA - Tluckova, Katarina; Testa Salmazo, Anita P; Bernecky, Carrie A
Transcription by RNA polymerase II (Pol II) can be repressed by noncoding RNA, including the human RNA Alu. However, the mechanism by which endogenous RNAs repress transcription remains unclear. Here we present cryo-electron microscopy structures of Pol II bound to Alu RNA, which reveal that Alu RNA mimics how DNA and RNA bind to Pol II during transcription elongation. Further, we show how domains of the general transcription factor TFIIF affect complex dynamics and control repressive activity. Together, we reveal how a non-coding RNA can regulate mammalian gene expression.

Spin-charge correlations in finite one-dimensional multiband Fermi systems - Becker, J. M.; Koutentakis, Georgios; Schmelcher, P. (Physical Review Research)
We investigate spin-charge separation of a spin- 1 2 Fermi system confined in a triple well where multiple bands are occupied. We assume that our finite fermionic system is close to fully spin polarized while being doped by a hole and an impurity fermion with opposite spin. Our setup involves ferromagnetic couplings among the particles in different bands, leading to the development of strong spin-transport correlations in an intermediate interaction regime. Interactions are then strong enough to lift the degeneracy among singlet and triplet spin configurations in the well of the spin impurity but not strong enough to prohibit hole-induced magnetic excitations to the singlet state. Despite the strong spin-hole correlations, the system exhibits spin-charge deconfinement allowing for long-range entanglement of the spatial and spin degrees of freedom.

Non-equilibrium dynamics of dipolar polarons - Volosniev, Artem; Bighin, Giacomo; Santos, Luis; Peña Ardila, Luisllu A. (SciPost Physics)
We study the out-of-equilibrium quantum dynamics of dipolar polarons, i.e., impurities immersed in a dipolar Bose-Einstein condensate, after a quench of the impurity-boson interaction. We show that the dipolar nature of the condensate and of the impurity results in anisotropic relaxation dynamics, in particular, anisotropic dressing of the polaron. More relevantly for cold-atom setups, quench dynamics is strongly affected by the interplay between dipolar anisotropy and trap geometry. Our findings pave the way for simulating impurities in anisotropic media utilizing experiments with dipolar mixtures.
Keywords: General Physics and Astronomy

Advanced motion tracking for interactive mass spectrometry imaging (IMSI) - Kluibenschedl, Florian; Ploner, Anna; Meisenbichler, Christina; Konrat, Robert; Müller, Thomas (International Journal of Mass Spectrometry)
Mass spectrometry imaging (MSI) is a powerful analytical technique for the two-dimensional (2D) localization of chemicals on surfaces. Conventional MSI experiments require to predefine the surface of interest based on photographic or microscopic images. Typically, these boundaries can no longer be changed or adjusted once the experiment has been started. In terms of a more interactive approach we recently developed a pen-like ionization interface which is directly connected to the mass spectrometer. The device allows the user to ionize chemicals by desorption electrospray ionization (DESI) and to freely move the interface over a surface of interest. A mini camera, which is mounted on the tip of the pen, magnifies the desorption area and enables a simple positioning of the pen. The combination of optical data from the camera module and chemical data obtained by mass analysis facilitates a novel type of imaging experiment: interactive mass spectrometry imaging (IMSI). For this application, we present a novel approach for a robust, optical flow-based motion detection. While the live video stream from the camera is used to track the pen's motion across the surface a post-acquisition algorithm correlates the coordinates of the pen trajectory with respective mass spectra obtained from a simultaneous mass spectrometric data acquisition. This algorithm is no longer dependent on a single, manually applied optical marker on the sample surface, which has to be visible on all video frames throughout the analysis. The advanced DESI-IMSI method was successfully tested on inkjet-printed letters as well as mouse brain tissue samples. Validation of the results was done by comparing DESI-IMSI with standard DESI-MSI data.

Dual role of FOXG1 in regulating gliogenesis in the developing neocortex via the FGF signalling pathway - Bose, Mahima; Suresh, Varun; Mishra, Urvi; Talwar, Ishita; Yadav, Anuradha; Biswas, Shiona; Hippenmeyer, Simon; Tole, Shubha (bioRxiv)
In the developing vertebrate central nervous system, neurons and glia typically arise sequentially from common progenitors. Here, we report that the transcription factor Forkhead Box G1 (Foxg1) regulates gliogenesis in the mouse neocortex via distinct cell-autonomous roles in progenitors and in postmitotic neurons that regulate different aspects of the gliogenic FGF signalling pathway. We demonstrate that loss of Foxg1 in cortical progenitors at neurogenic stages causes premature astrogliogenesis. We identify a novel FOXG1 target, the pro-gliogenic FGF pathway component Fgfr3, which is suppressed by FOXG1 cell-autonomously to maintain neurogenesis. Furthermore, FOXG1 can also suppress premature astrogliogenesis triggered by the augmentation of FGF signalling. We identify a second novel function of FOXG1 in regulating the expression of gliogenic ligand FGF18 in new born neocortical upper-layer neurons. Loss of FOXG1 in postmitotic neurons increases Fgf18 expression and enhances gliogenesis in the progenitors. These results fit well with the model that new born neurons secrete cues that trigger progenitors to produce the next wave of cell types, astrocytes. If FGF signalling is attenuated in Foxg1 null progenitors, they progress to oligodendrocyte production. Therefore, loss of FOXG1 transitions the progenitor to a gliogenic state, producing either astrocytes or oligodendrocytes depending on FGF signalling levels. Our results uncover how FOXG1 integrates extrinsic signalling via the FGF pathway to regulate the sequential generation of neurons, astrocytes, and oligodendrocytes in the cerebral cortex.

Transverse fluctuations control the assembly of semiflexible filaments - Sorichetti, Valerio; Lenz, Martin (Physical Review Letters)
The kinetics of the assembly of semiflexible filaments through end-to-end annealing is key to the structure of the cytoskeleton, but is not understood. We analyze this problem through scaling theory and simulations, and uncover a regime where filaments’ ends find each other through bending fluctuations without the need for the whole filament to diffuse. This results in a very substantial speedup of assembly in physiological regimes, and could help with understanding the dynamics of actin and intermediate filaments in biological processes such as wound healing and cell division.

Quantitative Steinitz theorem: A polynomial bound - Ivanov, Grigory; Naszódi, Márton (Bulletin of the London Mathematical Society)
The classical Steinitz theorem states that if the origin belongs to the interior of the convex hull of a set 𝑆⊂ℝ𝑑, then there are at most 2𝑑 points of 𝑆 whose convex hull contains the origin in the interior. Bárány, Katchalski,and Pach proved the following quantitative version of Steinitz’s theorem. Let 𝑄 be a convex polytope in ℝ𝑑 containing the standard Euclidean unit ball 𝐁𝑑. Then there exist at most 2𝑑 vertices of 𝑄 whose convex hull 𝑄′ satisfies 𝑟𝐁𝑑⊂𝑄′ with 𝑟⩾𝑑−2𝑑. They conjectured that 𝑟⩾𝑐𝑑−1∕2 holds with a universal constant 𝑐>0. We prove 𝑟⩾15𝑑2, the first polynomial lower bound on 𝑟. Furthermore, we show that 𝑟 is not greater than 2/√𝑑.

Metabolically regulated spiking could serve neuronal energy homeostasis and protect from reactive oxygen species - Chintaluri, Chaitanya; Vogels, Tim P (Proceedings of the National Academy of Sciences of the United States of America)
So-called spontaneous activity is a central hallmark of most nervous systems. Such non-causal firing is contrary to the tenet of spikes as a means of communication, and its purpose remains unclear. We propose that self-initiated firing can serve as a release valve to protect neurons from the toxic conditions arising in mitochondria from lower-than-baseline energy consumption. To demonstrate the viability of our hypothesis, we built a set of models that incorporate recent experimental results indicating homeostatic control of metabolic products—Adenosine triphosphate (ATP), adenosine diphosphate (ADP), and reactive oxygen species (ROS)—by changes in firing. We explore the relationship of metabolic cost of spiking with its effect on the temporal patterning of spikes and reproduce experimentally observed changes in intrinsic firing in the fruitfly dorsal fan-shaped body neuron in a model with ROS-modulated potassium channels. We also show that metabolic spiking homeostasis can produce indefinitely sustained avalanche dynamics in cortical circuits. Our theory can account for key features of neuronal activity observed in many studies ranging from ion channel function all the way to resting state dynamics. We finish with a set of experimental predictions that would confirm an integrated, crucial role for metabolically regulated spiking and firmly link metabolic homeostasis and neuronal function.

The structure of hippocampal CA1 interactions optimizes spatial coding across experience - Nardin, Michele; Csicsvari, Jozsef L; Tkačik, Gašper; Savin, Cristina (The Journal of Neuroscience)
Although much is known about how single neurons in the hippocampus represent an animal's position, how circuit interactions contribute to spatial coding is less well understood. Using a novel statistical estimator and theoretical modeling, both developed in the framework of maximum entropy models, we reveal highly structured CA1 cell-cell interactions in male rats during open field exploration. The statistics of these interactions depend on whether the animal is in a familiar or novel environment. In both conditions the circuit interactions optimize the encoding of spatial information, but for regimes that differ in the informativeness of their spatial inputs. This structure facilitates linear decodability, making the information easy to read out by downstream circuits. Overall, our findings suggest that the efficient coding hypothesis is not only applicable to individual neuron properties in the sensory periphery, but also to neural interactions in the central brain.

Evolutionary dynamics of mutants that modify population structure - Tkadlec, Josef; Kaveh, Kamran; Chatterjee, Krishnendu; Nowak, Martin A. (Journal of the Royal Society, Interface)
Natural selection is usually studied between mutants that differ in reproductive rate, but are subject to the same population structure. Here we explore how natural selection acts on mutants that have the same reproductive rate, but different population structures. In our framework, population structure is given by a graph that specifies where offspring can disperse. The invading mutant disperses offspring on a different graph than the resident wild-type. We find that more densely connected dispersal graphs tend to increase the invader’s fixation probability, but the exact relationship between structure and fixation probability is subtle. We present three main results. First, we prove that if both invader and resident are on complete dispersal graphs, then removing a single edge in the invader’s dispersal graph reduces its fixation probability. Second, we show that for certain island models higher invader’s connectivity increases its fixation probability, but the magnitude of the effect depends on the exact layout of the connections. Third, we show that for lattices the effect of different connectivity is comparable to that of different fitness: for large population size, the invader’s fixation probability is either constant or exponentially small, depending on whether it is more or less connected than the resident.

Guest encapsulation alters the thermodynamic landscape of a coordination host - Hema, Kuntrapakam; Grommet, Angela B.; Białek, Michał J.; Wang, Jinhua; Schneider, Laura; Drechsler, Christoph; Yanshyna, Oksana; Diskin-Posner, Yael; Clever, Guido H.; Klajn, Rafal (Journal of the American Chemical Society)
The architecture of self-assembled host molecules can profoundly affect the properties of the encapsulated guests. For example, a rigid cage with small windows can efficiently protect its contents from the environment; in contrast, tube-shaped, flexible hosts with large openings and an easily accessible cavity are ideally suited for catalysis. Here, we report a “Janus” nature of a Pd6L4 coordination host previously reported to exist exclusively as a tube isomer (T). We show that upon encapsulating various tetrahedrally shaped guests, T can reconfigure into a cage-shaped host (C) in quantitative yield. Extracting the guest affords empty C, which is metastable and spontaneously relaxes to T, and the T⇄C interconversion can be repeated for multiple cycles. Reversible toggling between two vastly different isomers paves the way toward controlling functional properties of coordination hosts “on demand”.

Microkinetic modeling with size-dependent and adsorbate-adsorbate interactions for the direct synthesis of H₂O₂ over Pd nanoparticles - Zhao, Jinyan; Yao, Zihao; Bunting, Rhys; Hu, P.; Wang, Jianguo (ACS Catalysis)
As a bottleneck in the direct synthesis of hydrogen peroxide, the development of an efficient palladium-based catalyst has garnered great attention. However, elusive active centers and reaction mechanism issues inhibit further optimization of its performance. In this work, advanced microkinetic modeling with the adsorbate–adsorbate interaction and nanoparticle size effect based on first-principles calculations is developed. A full mechanism uncovering the significance of adsorbate–adsorbate interaction is determined on Pd nanoparticles. We demonstrate unambiguously that Pd(100) with main coverage species of O2 and H is beneficial to H2O2 production, being consistent with experimental operando observation, while H2O forms on Pd(111) covered by O species and Pd(211) covered by O and OH species. Kinetic analyses further enable quantitative estimation of the influence of temperature, pressure, and particle size. Large-size Pd nanoparticles are found to achieve a high H2O2 reaction rate when the operating conditions are moderate temperature and higher oxygen partial pressure. We reveal that specific facets of the Pd nanoparticles are crucial factors for their selectivity and activity. Consistent with the experiment, the production of H2O2 is discovered to be more favorable on Pd nanoparticles containing Pd(100) facets. The ratio of H2/O2 induces substantial variations in the coverage of intermediates of O2 and H on Pd(100), resulting in a change in product selectivity.

Functional CLT for non-Hermitian random matrices - Erdös, László; Ji, Hong Chang (Annales de l'institut Henri Poincare (B) Probability and Statistics)
For large dimensional non-Hermitian random matrices X with real or complex independent, identically distributed, centered entries, we consider the fluctuations of f (X) as a matrix where f is an analytic function around the spectrum of X. We prove that for a generic bounded square matrix A, the quantity Tr f (X)A exhibits Gaussian fluctuations as the matrix size grows to infinity, which consists of two independent modes corresponding to the tracial and traceless parts of A. We find a new formula for the variance of the traceless part that involves the Frobenius norm of A and the L2-norm of f on the boundary of the limiting spectrum.

Absence of excited eigenvalues for Fröhlich type polaron models at weak coupling - Seiringer, Robert (Journal of Spectral Theory)
We consider a class of polaron models, including the Fröhlich model, at zero total momentum, and show that at sufficiently weak coupling there are no excited eigenvalues below the essential spectrum.

Ab-initio stability of Iridium based newly proposed full and quaternary heusler alloys - Gupta, Shyam Lal; Singh, Saurabh; Kumar, Sumit; Anupam, Unknown; Thakur, Samjeet Singh; Kumar, Ashish; Panwar, Sanjay; Diwaker, D. (Physica B: Condensed Matter)
In order to demonstrate the stability of newly proposed iridium-based Ir2Cr(In,Sn) and IrRhCr(In,Sn) heusler alloys, we present ab-initio analysis of these alloys by examining various properties to prove their stability. The stability of these alloys can be inferred from different cohesive and formation energies as well as positive phonon frequencies. Their electronic structure results indicate that they are semi-metals in nature. The magnetic moments are computed using the Slater-Pauling formula and exhibit a high value, with the Cr atom contributing the most in all alloys. Mulliken’s charge analysis results show that our alloys contain a range of linkages, mainly ionic and covalent ones. The ductility and mechanical stability of these alloys are confirmed by elastic constants viz. Poisson’s ratio, Pugh’s ratio, and many different types of elastic moduli.

Criticality of neuronal avalanches in human sleep and their relationship with sleep macro- and micro-architecture - Scarpetta, Silvia; Morrisi, Niccolò; Mutti, Carlotta; Azzi, Nicoletta; Trippi, Irene; Ciliento, Rosario; Apicella, Ilenia; Messuti, Giovanni; Angiolelli, Marianna; Lombardi, Fabrizio; Parrino, Liborio; Vaudano, Anna Elisabetta (iScience)
Sleep plays a key role in preserving brain function, keeping the brain network in a state that ensures optimal computational capabilities. Empirical evidence indicates that such a state is consistent with criticality, where scale-free neuronal avalanches emerge. However, the relationship between sleep, emergent avalanches, and criticality remains poorly understood. Here we fully characterize the critical behavior of avalanches during sleep, and study their relationship with the sleep macro- and micro-architecture, in particular the cyclic alternating pattern (CAP). We show that avalanche size and duration distributions exhibit robust power laws with exponents approximately equal to −3/2 e −2, respectively. Importantly, we find that sizes scale as a power law of the durations, and that all critical exponents for neuronal avalanches obey robust scaling relations, which are consistent with the mean-field directed percolation universality class. Our analysis demonstrates that avalanche dynamics depends on the position within the NREM-REM cycles, with the avalanche density increasing in the descending phases and decreasing in the ascending phases of sleep cycles. Moreover, we show that, within NREM sleep, avalanche occurrence correlates with CAP activation phases, particularly A1, which are the expression of slow wave sleep propensity and have been proposed to be beneficial for cognitive processes. The results suggest that neuronal avalanches, and thus tuning to criticality, actively contribute to sleep development and play a role in preserving network function. Such findings, alongside characterization of the universality class for avalanches, open new avenues to the investigation of functional role of criticality during sleep with potential clinical application. Significance statement We fully characterize the critical behavior of neuronal avalanches during sleep, and show that avalanches follow precise scaling laws that are consistent with the mean-field directed percolation universality class. The analysis provides first evidence of a functional relationship between avalanche occurrence, slow-wave sleep dynamics, sleep stage transitions and occurrence of CAP phase A during NREM sleep. Because CAP is considered one of the major guardians of NREM sleep that allows the brain to dynamically react to external perturbation and contributes to the cognitive consolidation processes occurring in sleep, our observations suggest that neuronal avalanches at criticality are associated with flexible response to external inputs and to cognitive processes, a key assumption of the critical brain hypothesis.

Trade-offs between immunity and competitive ability in fighting ant males - Metzler, Sina; Kirchner, Jessica; Grasse, Anna V; Cremer, Sylvia (BMC Ecology and Evolution)
Background: Fighting disease while fighting rivals exposes males to constraints and tradeoffs during male-male competition. We here tested how both the stage and intensity of infection with the fungal pathogen Metarhizium robertsii interfered with fighting success in Cardiocondyla obscurior ant males. Males of this species have evolved long lifespans during which they can gain many matings with the young queens of the colony, if successful in male-male competition. Since male fights occur inside the colony, the outcome of male-male competition can further be biased by interference of the colony’s worker force. Results: We found that severe, but not yet mild, infection strongly impaired male fighting success. In late-stage infection, this could be attributed to worker aggression directed towards the infected rather than the healthy male and an already very high male morbidity even in the absence of fighting. Shortly after pathogen exposure, however, male mortality was particularly increased during combat. Since these males mounted a strong immune response, their reduced fighting success suggests a trade-off between immune investment and competitive ability already early in the infection. Even if the males themselves showed no difference in the number of attacks they raised against their healthy rivals across infection stages and levels, severely infected males were thus losing in male-male competition from an early stage of infection on. Conclusions: Males of the ant C. obscurior have evolved high immune investment, triggering an effective immune response very fast after fungal exposure. This allows them to cope with mild pathogen exposures without cost to their success in male-male competition, and hence to gain multiple mating opportunities with the emerging virgin queens of the colony. Under severe infection, however, they are weak fighters and rarely survive a combat already at early infection when raising an immune response, as well as at progressed infection, when they are morbid and preferentially targeted by worker aggression. Workers thereby remove males that pose a future disease threat by biasing male-male competition. Our study thus revealed a novel social immunity mechanism how social insect workers protect the colony against disease risk.

Local cooling and drying induced by Himalayan glaciers under global warming - Salerno, Franco; Guyennon, Nicolas; Yang, Kun; Shaw, Thomas; Lin, Changgui; Colombo, Nicola; Romano, Emanuele; Gruber, Stephan; Bolch, Tobias; Alessandri, Andrea; Cristofanelli, Paolo; Putero, Davide; et al. (Nature Geoscience)
Understanding the response of Himalayan glaciers to global warming is vital because of their role as a water source for the Asian subcontinent. However, great uncertainties still exist on the climate drivers of past and present glacier changes across scales. Here, we analyse continuous hourly climate station data from a glacierized elevation (Pyramid station, Mount Everest) since 1994 together with other ground observations and climate reanalysis. We show that a decrease in maximum air temperature and precipitation occurred during the last three decades at Pyramid in response to global warming. Reanalysis data suggest a broader occurrence of this effect in the glacierized areas of the Himalaya. We hypothesize that the counterintuitive cooling is caused by enhanced sensible heat exchange and the associated increase in glacier katabatic wind, which draws cool air downward from higher elevations. The stronger katabatic winds have also lowered the elevation of local wind convergence, thereby diminishing precipitation in glacial areas and negatively affecting glacier mass balance. This local cooling may have partially preserved glaciers from melting and could help protect the periglacial environment.

Modulatory mechanisms of TARP γ8-selective AMPA receptor therapeutics - Zhang, Danyang; Lape, Remigijus; Shaikh, Saher A.; Kohegyi, Bianka K.; Watson, Jake; Cais, Ondrej; Nakagawa, Terunaga; Greger, Ingo H. (Nature Communications)
AMPA glutamate receptors (AMPARs) mediate excitatory neurotransmission throughout the brain. Their signalling is uniquely diversified by brain region-specific auxiliary subunits, providing an opportunity for the development of selective therapeutics. AMPARs associated with TARP γ8 are enriched in the hippocampus, and are targets of emerging anti-epileptic drugs. To understand their therapeutic activity, we determined cryo-EM structures of the GluA1/2-γ8 receptor associated with three potent, chemically diverse ligands. We find that despite sharing a lipid-exposed and water-accessible binding pocket, drug action is differentially affected by binding-site mutants. Together with patch-clamp recordings and MD simulations we also demonstrate that ligand-triggered reorganisation of the AMPAR-TARP interface contributes to modulation. Unexpectedly, one ligand (JNJ-61432059) acts bifunctionally, negatively affecting GluA1 but exerting positive modulatory action on GluA2-containing AMPARs, in a TARP stoichiometry-dependent manner. These results further illuminate the action of TARPs, demonstrate the sensitive balance between positive and negative modulatory action, and provide a mechanistic platform for development of both positive and negative selective AMPAR modulators.

Source data for Metzler et al, 2023: Trade-offs between immunity and competitive ability in fighting ant males - Cremer, Sylvia
See Readme File for further information.

Effects of urban living environments on mental health in adults - Xu, Jiayuan; Liu, Nana; Polemiti, Elli; Garcia-Mondragon, Liliana; Tang, Jie; Liu, Xiaoxuan; Lett, Tristram; Yu, Le; Nöthen, Markus M.; Feng, Jianfeng; Yu, Chunshui; Marquand, Andre; et al. (Nature Medicine)
Urban-living individuals are exposed to many environmental factors that may combine and interact to influence mental health. While individual factors of an urban environment have been investigated in isolation, no attempt has been made to model how complex, real-life exposure to living in the city relates to brain and mental health, and how this is moderated by genetic factors. Using the data of 156,075 participants from the UK Biobank, we carried out sparse canonical correlation analyses to investigate the relationships between urban environments and psychiatric symptoms. We found an environmental profile of social deprivation, air pollution, street network and urban land-use density that was positively correlated with an affective symptom group (r = 0.22, Pperm < 0.001), mediated by brain volume differences consistent with reward processing, and moderated by genes enriched for stress response, including CRHR1, explaining 2.01% of the variance in brain volume differences. Protective factors such as greenness and generous destination accessibility were negatively correlated with an anxiety symptom group (r = 0.10, Pperm < 0.001), mediated by brain regions necessary for emotion regulation and moderated by EXD3, explaining 1.65% of the variance. The third urban environmental profile was correlated with an emotional instability symptom group (r = 0.03, Pperm < 0.001). Our findings suggest that different environmental profiles of urban living may influence specific psychiatric symptom groups through distinct neurobiological pathways.

Learning deposition policies for fused multi-material 3D printing - Liao, Kang; Tricard, Thibault; Piovarci, Michael; Seidel, Hans-Peter; Babaei, Vahid (2023 IEEE International Conference on Robotics and Automation)
3D printing based on continuous deposition of materials, such as filament-based 3D printing, has seen widespread adoption thanks to its versatility in working with a wide range of materials. An important shortcoming of this type of technology is its limited multi-material capabilities. While there are simple hardware designs that enable multi-material printing in principle, the required software is heavily underdeveloped. A typical hardware design fuses together individual materials fed into a single chamber from multiple inlets before they are deposited. This design, however, introduces a time delay between the intended material mixture and its actual deposition. In this work, inspired by diverse path planning research in robotics, we show that this mechanical challenge can be addressed via improved printer control. We propose to formulate the search for optimal multi-material printing policies in a reinforcement learning setup. We put forward a simple numerical deposition model that takes into account the non-linear material mixing and delayed material deposition. To validate our system we focus on color fabrication, a problem known for its strict requirements for varying material mixtures at a high spatial frequency. We demonstrate that our learned control policy outperforms state-of-the-art hand-crafted algorithms.
Keywords: reinforcement learning; deposition; control; color; multi-filament

Divergent molecular signatures in fish Bouncer proteins define cross-fertilization boundaries - Gert, Krista R.B.; Panser, Karin; Surm, Joachim; Steinmetz, Benjamin S.; Schleiffer, Alexander; Jovine, Luca; Moran, Yehu; Kondrashov, Fyodor; Pauli, Andrea (Nature Communications)
Molecular compatibility between gametes is a prerequisite for successful fertilization. As long as a sperm and egg can recognize and bind each other via their surface proteins, gamete fusion may occur even between members of separate species, resulting in hybrids that can impact speciation. The egg membrane protein Bouncer confers species specificity to gamete interactions between medaka and zebrafish, preventing their cross-fertilization. Here, we leverage this specificity to uncover distinct amino acid residues and N-glycosylation patterns that differentially influence the function of medaka and zebrafish Bouncer and contribute to cross-species incompatibility. Curiously, in contrast to the specificity observed for medaka and zebrafish Bouncer, seahorse and fugu Bouncer are compatible with both zebrafish and medaka sperm, in line with the pervasive purifying selection that dominates Bouncer’s evolution. The Bouncer-sperm interaction is therefore the product of seemingly opposing evolutionary forces that, for some species, restrict fertilization to closely related fish, and for others, allow broad gamete compatibility that enables hybridization.

Some effectivity results for primitive divisors of elliptic divisibility sequences - Verzobio, Matteo (Pacific Journal of Mathematics)
Let P be a nontorsion point on an elliptic curve defined over a number field K and consider the sequence Bnn∈N of the denominators of x(nP). We prove that every term of the sequence of the Bn has a primitive divisor for n greater than an effectively computable constant that we will explicitly compute. This constant will depend only on the model defining the curve.

A Mecke-type characterization of the Dirichlet–Ferguson measure - Dello Schiavo, Lorenzo; Lytvynov, Eugene (Electronic Communications in Probability)
We prove a characterization of the Dirichlet–Ferguson measure over an arbitrary finite diffuse measure space. We provide an interpretation of this characterization in analogy with the Mecke identity for Poisson point processes.

Multiple packing: Lower bounds via infinite constellations - Zhang, Yihan; Vatedka, Shashank (IEEE Transactions on Information Theory)
We study the problem of high-dimensional multiple packing in Euclidean space. Multiple packing is a natural generalization of sphere packing and is defined as follows. Let N > 0 and L ∈ Z ≽2 . A multiple packing is a set C of points in R n such that any point in R n lies in the intersection of at most L – 1 balls of radius √ nN around points in C . Given a well-known connection with coding theory, multiple packings can be viewed as the Euclidean analog of list-decodable codes, which are well-studied for finite fields. In this paper, we derive the best known lower bounds on the optimal density of list-decodable infinite constellations for constant L under a stronger notion called average-radius multiple packing. To this end, we apply tools from high-dimensional geometry and large deviation theory.

Correlation energy of a weakly interacting Fermi gas with large interaction potential - Benedikter, Niels P; Porta, Marcello; Schlein, Benjamin; Seiringer, Robert (Archive for Rational Mechanics and Analysis)
Recently the leading order of the correlation energy of a Fermi gas in a coupled mean-field and semiclassical scaling regime has been derived, under the assumption of an interaction potential with a small norm and with compact support in Fourier space. We generalize this result to large interaction potentials, requiring only |⋅|V^∈ℓ1(Z3). Our proof is based on approximate, collective bosonization in three dimensions. Significant improvements compared to recent work include stronger bounds on non-bosonizable terms and more efficient control on the bosonization of the kinetic energy.

Weak Edgeworth expansion for the mean-field Bose gas - Bossmann, Lea; Petrat, Sören P (Letters in Mathematical Physics)
We consider the ground state and the low-energy excited states of a system of N identical bosons with interactions in the mean-field scaling regime. For the ground state, we derive a weak Edgeworth expansion for the fluctuations of bounded one-body operators, which yields corrections to a central limit theorem to any order in 1/N−−√. For suitable excited states, we show that the limiting distribution is a polynomial times a normal distribution, and that higher-order corrections are given by an Edgeworth-type expansion.

Inductively shunted transmons exhibit noise insensitive plasmon states and a fluxon decay exceeding 3 hours - Hassani, Farid; Peruzzo, Matilda; Kapoor, Lucky; Trioni, Andrea; Zemlicka, Martin; Fink, Johannes M (Nature Communications)
Currently available quantum processors are dominated by noise, which severely limits their applicability and motivates the search for new physical qubit encodings. In this work, we introduce the inductively shunted transmon, a weakly flux-tunable superconducting qubit that offers charge offset protection for all levels and a 20-fold reduction in flux dispersion compared to the state-of-the-art resulting in a constant coherence over a full flux quantum. The parabolic confinement provided by the inductive shunt as well as the linearity of the geometric superinductor facilitates a high-power readout that resolves quantum jumps with a fidelity and QND-ness of >90% and without the need for a Josephson parametric amplifier. Moreover, the device reveals quantum tunneling physics between the two prepared fluxon ground states with a measured average decay time of up to 3.5 h. In the future, fast time-domain control of the transition matrix elements could offer a new path forward to also achieve full qubit control in the decay-protected fluxon basis.

Approximate message passing for multi-layer estimation in rotationally invariant models - Xu, Yizhou; Hou, Tian Qi; Liang, Shan Suo; Mondelli, Marco (2023 IEEE Information Theory Workshop)
We consider the problem of reconstructing the signal and the hidden variables from observations coming from a multi-layer network with rotationally invariant weight matrices. The multi-layer structure models inference from deep generative priors, and the rotational invariance imposed on the weights generalizes the i.i.d. Gaussian assumption by allowing for a complex correlation structure, which is typical in applications. In this work, we present a new class of approximate message passing (AMP) algorithms and give a state evolution recursion which precisely characterizes their performance in the large system limit. In contrast with the existing multi-layer VAMP (ML-VAMP) approach, our proposed AMP – dubbed multilayer rotationally invariant generalized AMP (ML-RI-GAMP) – provides a natural generalization beyond Gaussian designs, in the sense that it recovers the existing Gaussian AMP as a special case. Furthermore, ML-RI-GAMP exhibits a significantly lower complexity than ML-VAMP, as the computationally intensive singular value decomposition is replaced by an estimation of the moments of the design matrices. Finally, our numerical results show that this complexity gain comes at little to no cost in the performance of the algorithm.

As-Continuous-As-Possible extrusion-based fabrication of surface models - Zhong, Fanchao; Xu, Yonglai; Zhao, Haisen; Lu, Lin (ACM Transactions on Graphics)
In this study, we propose a computational framework for optimizing the continuity of the toolpath in fabricating surface models on an extrusion-based 3D printer. Toolpath continuity is a critical issue that influences both the quality and the efficiency of extrusion-based fabrication. Transfer moves lead to rough and bumpy surfaces, where this phenomenon worsens for materials with large viscosity, like clay. The effects of continuity on the surface models are even more severe in terms of the quality of the surface and the stability of the model. We introduce a criterion called the one–path patch (OPP) to represent a patch on the surface of the shell that can be traversed along one path by considering the constraints on fabrication. We study the properties of the OPPs and their merging operations to propose a bottom-up OPP merging procedure to decompose the given shell surface into a minimal number of OPPs, and to generate the “as-continuous-as-possible” (ACAP) toolpath. Furthermore, we augment the path planning algorithm with a curved-layer printing scheme that reduces staircase defects and improves the continuity of the toolpath by connecting multiple segments. We evaluated the ACAP algorithm on ceramic and thermoplastic materials, and the results showed that it improves the fabrication of surface models in terms of both efficiency and surface quality.

Noncommutative Bohnenblust–Hille inequalities - Volberg, Alexander; Zhang, Haonan (Mathematische Annalen)
Bohnenblust–Hille inequalities for Boolean cubes have been proven with dimension-free constants that grow subexponentially in the degree (Defant et al. in Math Ann 374(1):653–680, 2019). Such inequalities have found great applications in learning low-degree Boolean functions (Eskenazis and Ivanisvili in Proceedings of the 54th annual ACM SIGACT symposium on theory of computing, pp 203–207, 2022). Motivated by learning quantum observables, a qubit analogue of Bohnenblust–Hille inequality for Boolean cubes was recently conjectured in Rouzé et al. (Quantum Talagrand, KKL and Friedgut’s theorems and the learnability of quantum Boolean functions, 2022. arXiv preprint arXiv:2209.07279). The conjecture was resolved in Huang et al. (Learning to predict arbitrary quantum processes, 2022. arXiv preprint arXiv:2210.14894). In this paper, we give a new proof of these Bohnenblust–Hille inequalities for qubit system with constants that are dimension-free and of exponential growth in the degree. As a consequence, we obtain a junta theorem for low-degree polynomials. Using similar ideas, we also study learning problems of low degree quantum observables and Bohr’s radius phenomenon on quantum Boolean cubes.

Some convexity and monotonicity results of trace functionals - Zhang, Haonan (Annales Henri Poincare)
In this paper, we prove the convexity of trace functionals (A,B,C)↦Tr|BpACq|s, for parameters (p, q, s) that are best possible, where B and C are any n-by-n positive-definite matrices, and A is any n-by-n matrix. We also obtain the monotonicity versions of trace functionals of this type. As applications, we extend some results in Carlen et al. (Linear Algebra Appl 490:174–185, 2016), Hiai and Petz (Publ Res Inst Math Sci 48(3):525-542, 2012) and resolve a conjecture in Al-Rashed and Zegarliński (Infin Dimens Anal Quantum Probab Relat Top 17(4):1450029, 2014) in the matrix setting. Other conjectures in Al-Rashed and Zegarliński (Infin Dimens Anal Quantum Probab Relat Top 17(4):1450029, 2014) will also be discussed. We also show that some related trace functionals are not concave in general. Such concavity results were expected to hold in different problems.

The effect of environmental information on evolution of cooperation in stochastic games - Kleshnina, Maria; Hilbe, Christian; Simsa, Stepan; Chatterjee, Krishnendu; Nowak, Martin A. (Nature Communications)
Many human interactions feature the characteristics of social dilemmas where individual actions have consequences for the group and the environment. The feedback between behavior and environment can be studied with the framework of stochastic games. In stochastic games, the state of the environment can change, depending on the choices made by group members. Past work suggests that such feedback can reinforce cooperative behaviors. In particular, cooperation can evolve in stochastic games even if it is infeasible in each separate repeated game. In stochastic games, participants have an interest in conditioning their strategies on the state of the environment. Yet in many applications, precise information about the state could be scarce. Here, we study how the availability of information (or lack thereof) shapes evolution of cooperation. Already for simple examples of two state games we find surprising effects. In some cases, cooperation is only possible if there is precise information about the state of the environment. In other cases, cooperation is most abundant when there is no information about the state of the environment. We systematically analyze all stochastic games of a given complexity class, to determine when receiving information about the environment is better, neutral, or worse for evolution of cooperation.

Trap spaces of multi-valued networks: Definition, computation, and applications - Trinh, Van Giang; Benhamou, Belaid; Henzinger, Thomas A; Pastva, Samuel (Bioinformatics)
Motivation: Boolean networks are simple but efficient mathematical formalism for modelling complex biological systems. However, having only two levels of activation is sometimes not enough to fully capture the dynamics of real-world biological systems. Hence, the need for multi-valued networks (MVNs), a generalization of Boolean networks. Despite the importance of MVNs for modelling biological systems, only limited progress has been made on developing theories, analysis methods, and tools that can support them. In particular, the recent use of trap spaces in Boolean networks made a great impact on the field of systems biology, but there has been no similar concept defined and studied for MVNs to date. Results: In this work, we generalize the concept of trap spaces in Boolean networks to that in MVNs. We then develop the theory and the analysis methods for trap spaces in MVNs. In particular, we implement all proposed methods in a Python package called trapmvn. Not only showing the applicability of our approach via a realistic case study, we also evaluate the time efficiency of the method on a large collection of real-world models. The experimental results confirm the time efficiency, which we believe enables more accurate analysis on larger and more complex multi-valued models.

The yeast endocytic early/sorting compartment exists as an independent sub-compartment within the trans-Golgi network - Toshima, Junko Y.; Tsukahara, Ayana; Nagano, Makoto; Tojima, Takuro; Siekhaus, Daria E; Nakano, Akihiko; Toshima, Jiro (eLife)
Although budding yeast has been extensively used as a model organism for studying organelle functions and intracellular vesicle trafficking, whether it possesses an independent endocytic early/sorting compartment that sorts endocytic cargos to the endo-lysosomal pathway or the recycling pathway has long been unclear. The structure and properties of the endocytic early/sorting compartment differ significantly between organisms; in plant cells, the trans-Golgi network (TGN) serves this role, whereas in mammalian cells a separate intracellular structure performs this function. The yeast syntaxin homolog Tlg2p, widely localizing to the TGN and endosomal compartments, is presumed to act as a Q-SNARE for endocytic vesicles, but which compartment is the direct target for endocytic vesicles remained unanswered. Here we demonstrate by high-speed and high-resolution 4D imaging of fluorescently labeled endocytic cargos that the Tlg2p-residing compartment within the TGN functions as the early/sorting compartment. After arriving here, endocytic cargos are recycled to the plasma membrane or transported to the yeast Rab5-residing endosomal compartment through the pathway requiring the clathrin adaptors GGAs. Interestingly, Gga2p predominantly localizes at the Tlg2p-residing compartment, and the deletion of GGAs has little effect on another TGN region where Sec7p is present but suppresses dynamics of the Tlg2-residing early/sorting compartment, indicating that the Tlg2p- and Sec7p-residing regions are discrete entities in the mutant. Thus, the Tlg2p-residing region seems to serve as an early/sorting compartment and function independently of the Sec7p-residing region within the TGN.

Eigenstate thermalisation hypothesis for translation invariant spin systems - Sugimoto, Shoki; Henheik, Sven Joscha; Riabov, Volodymyr; Erdös, László (Journal of Statistical Physics)
We prove the Eigenstate Thermalisation Hypothesis (ETH) for local observables in a typical translation invariant system of quantum spins with L-body interactions, where L is the number of spins. This mathematically verifies the observation first made by Santos and Rigol (Phys Rev E 82(3):031130, 2010, https://doi.org/10.1103/PhysRevE.82.031130) that the ETH may hold for systems with additional translational symmetries for a naturally restricted class of observables. We also present numerical support for the same phenomenon for Hamiltonians with local interaction.

Magnetic impurity in a one-dimensional few-fermion system - Rammelmüller, Lukas; Huber, David; Čufar, Matija; Brand, Joachim; Hammer, Hans-Werner; Volosniev, Artem (SciPost Physics)
We present a numerical analysis of spin-1/2 fermions in a one-dimensional harmonic potential in the presence of a magnetic point-like impurity at the center of the trap. The model represents a few-body analogue of a magnetic impurity in the vicinity of an s-wave superconductor. Already for a few particles we find a ground-state level crossing between sectors with different fermion parities. We interpret this crossing as a few-body precursor of a quantum phase transition, which occurs when the impurity "breaks" a Cooper pair. This picture is further corroborated by analyzing density-density correlations in momentum space. Finally, we discuss how the system may be realized with existing cold-atoms platforms.
Keywords: General Physics and Astronomy

Direct path from turbulence to time-periodic solutions - Paranjape, Chaitanya S; Yalniz, Gökhan; Duguet, Yohann; Budanur, Nazmi B; Hof, Björn (Physical Review Letters)
Viscous flows through pipes and channels are steady and ordered until, with increasing velocity, the laminar motion catastrophically breaks down and gives way to turbulence. How this apparently discontinuous change from low- to high-dimensional motion can be rationalized within the framework of the Navier-Stokes equations is not well understood. Exploiting geometrical properties of transitional channel flow we trace turbulence to far lower Reynolds numbers (Re) than previously possible and identify the complete path that reversibly links fully turbulent motion to an invariant solution. This precursor of turbulence destabilizes rapidly with Re, and the accompanying explosive increase in attractor dimension effectively marks the transition between deterministic and de facto stochastic dynamics.
Keywords: General Physics and Astronomy

Stochastic motion and transcriptional dynamics of pairs of distal DNA loci on a compacted chromosome - Brückner, David; Chen, Hongtao; Barinov, Lev; Zoller, Benjamin; Gregor, Thomas (Science)
Chromosomes in the eukaryotic nucleus are highly compacted. However, for many functional processes, including transcription initiation, the pairwise motion of distal chromosomal elements such as enhancers and promoters is essential and necessitates dynamic fluidity. Here, we used a live-imaging assay to simultaneously measure the positions of pairs of enhancers and promoters and their transcriptional output while systematically varying the genomic separation between these two DNA loci. Our analysis reveals the coexistence of a compact globular organization and fast subdiffusive dynamics. These combined features cause an anomalous scaling of polymer relaxation times with genomic separation leading to long-ranged correlations. Thus, encounter times of DNA loci are much less dependent on genomic distance than predicted by existing polymer models, with potential consequences for eukaryotic gene expression.

kleshnina/stochgames_info: The effect of environmental information on evolution of cooperation in stochastic games - Kleshnina, Maria

Magnetic activity evolution of solar-like stars. I. Sph–age relation derived from Kepler observations - Mathur, Savita; Claytor, Zachary R.; Santos, Ângela R. G.; García, Rafael A.; Amard, Louis; Bugnet, Lisa Annabelle; Corsaro, Enrico; Bonanno, Alfio; Breton, Sylvain N.; Godoy-Rivera, Diego; Pinsonneault, Marc H.; van Saders, Jennifer (The Astrophysical Journal)
The ages of solar-like stars have been at the center of many studies such as exoplanet characterization or Galactic-archeology. While ages are usually computed from stellar evolution models, relations linking ages to other stellar properties, such as rotation and magnetic activity, have been investigated. With the large catalog of 55,232 rotation periods, Prot, and photometric magnetic activity index, Sph from Kepler data, we have the opportunity to look for such magneto-gyro-chronology relations. Stellar ages are obtained with two stellar evolution codes that include treatment of angular momentum evolution, hence using Prot as input in addition to classical atmospheric parameters. We explore two different ways of predicting stellar ages on three subsamples with spectroscopic observations: solar analogs, late-F and G dwarfs, and K dwarfs. We first perform a Bayesian analysis to derive relations between Sph and ages between 1 and 5 Gyr, and other stellar properties. For late-F and G dwarfs, and K dwarfs, the multivariate regression favors the model with Prot and Sph with median differences of 0.1% and 0.2%, respectively. We also apply Machine Learning techniques with a Random Forest algorithm to predict ages up to 14 Gyr with the same set of input parameters. For late-F, G and K dwarfs together, predicted ages are on average within 5.3% of the model ages and improve to 3.1% when including Prot. These are very promising results for a quick age estimation for solar-like stars with photometric observations, especially with current and future space missions.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Scientists without borders: Lessons from Ukraine - Wolfsberger, Walter; Chhugani, Karishma; Shchubelka, Khrystyna; Frolova, Alina; Salyha, Yuriy; Zlenko, Oksana; Arych, Mykhailo; Dziuba, Dmytro; Parkhomenko, Andrii; Smolanka, Volodymyr; Gümüş, Zeynep H.; Sezgin, Efe; et al. (GigaScience)
Conflicts and natural disasters affect entire populations of the countries involved and, in addition to the thousands of lives destroyed, have a substantial negative impact on the scientific advances these countries provide. The unprovoked invasion of Ukraine by Russia, the devastating earthquake in Turkey and Syria, and the ongoing conflicts in the Middle East are just a few examples. Millions of people have been killed or displaced, their futures uncertain. These events have resulted in extensive infrastructure collapse, with loss of electricity, transportation, and access to services. Schools, universities, and research centers have been destroyed along with decades’ worth of data, samples, and findings. Scholars in disaster areas face short- and long-term problems in terms of what they can accomplish now for obtaining grants and for employment in the long run. In our interconnected world, conflicts and disasters are no longer a local problem but have wide-ranging impacts on the entire world, both now and in the future. Here, we focus on the current and ongoing impact of war on the scientific community within Ukraine and from this draw lessons that can be applied to all affected countries where scientists at risk are facing hardship. We present and classify examples of effective and feasible mechanisms used to support researchers in countries facing hardship and discuss how these can be implemented with help from the international scientific community and what more is desperately needed. Reaching out, providing accessible training opportunities, and developing collaborations should increase inclusion and connectivity, support scientific advancements within affected communities, and expedite postwar and disaster recovery.

Order 5 Brauer–Manin obstructions to the integral Hasse principle on log K3 surfaces - Lyczak, Julian (Annales de l'Institut Fourier)
We construct families of log K3 surfaces and study the arithmetic of their members. We use this to produce explicit surfaces with an order 5 Brauer–Manin obstruction to the integral Hasse principle.

The crossing Tverberg theorem - Fulek, Radoslav; Gärtner, Bernd; Kupavskii, Andrey; Valtr, Pavel; Wagner, Uli (Discrete and Computational Geometry)
The Tverberg theorem is one of the cornerstones of discrete geometry. It states that, given a set X of at least (d+1)(r−1)+1 points in Rd, one can find a partition X=X1∪⋯∪Xr of X, such that the convex hulls of the Xi, i=1,…,r, all share a common point. In this paper, we prove a trengthening of this theorem that guarantees a partition which, in addition to the above, has the property that the boundaries of full-dimensional convex hulls have pairwise nonempty intersections. Possible generalizations and algorithmic aspects are also discussed. As a concrete application, we show that any n points in the plane in general position span ⌊n/3⌋ vertex-disjoint triangles that are pairwise crossing, meaning that their boundaries have pairwise nonempty intersections; this number is clearly best possible. A previous result of Álvarez-Rebollar et al. guarantees ⌊n/6⌋pairwise crossing triangles. Our result generalizes to a result about simplices in Rd, d≥2.

Spectrum of Lévy–Khintchine random laplacian matrices - Campbell, Andrew J; O’Rourke, Sean (Journal of Theoretical Probability)
We consider the spectrum of random Laplacian matrices of the form Ln=An−Dn where An is a real symmetric random matrix and Dn is a diagonal matrix whose entries are equal to the corresponding row sums of An. If An is a Wigner matrix with entries in the domain of attraction of a Gaussian distribution, the empirical spectral measure of Ln is known to converge to the free convolution of a semicircle distribution and a standard real Gaussian distribution. We consider real symmetric random matrices An with independent entries (up to symmetry) whose row sums converge to a purely non-Gaussian infinitely divisible distribution, which fall into the class of Lévy–Khintchine random matrices first introduced by Jung [Trans Am Math Soc, 370, (2018)]. Our main result shows that the empirical spectral measure of Ln converges almost surely to a deterministic limit. A key step in the proof is to use the purely non-Gaussian nature of the row sums to build a random operator to which Ln converges in an appropriate sense. This operator leads to a recursive distributional equation uniquely describing the Stieltjes transform of the limiting empirical spectral measure.

Magnetotropic susceptibility - Shekhter, A.; Mcdonald, R. D.; Ramshaw, B. J.; Modic, Kimberly A (Physical Review B)
The magnetotropic susceptibility is the thermodynamic coefficient associated with the rotational anisotropy of the free energy in an external magnetic field and is closely related to the magnetic susceptibility. It emerges naturally in frequency-shift measurements of oscillating mechanical cantilevers, which are becoming an increasingly important tool in the quantitative study of the thermodynamics of modern condensed-matter systems. Here we discuss the basic properties of the magnetotropic susceptibility as they relate to the experimental aspects of frequency-shift measurements, as well as to the interpretation of those experiments in terms of the intrinsic properties of the system under study.

Special Collection: Photocatalytic synthesis - Næsborg, Line; Pieber, Bartholomäus; Wenger, Oliver S. (ChemCatChem)
This Special Collection is dedicated to the field of photocatalytic synthesis and contains a diverse selection of original research contributions. It includes studies on catalyst development, mechanistic investigations, method development and the use of enabling technologies, illustrating the many facets of state-of-the-art research in photocatalytic synthesis. Further, emerging topics are surveyed and discussed in three reviews and a concept article.

Optical and electronic signal stabilization of plasmonic fiber optic gate electrodes: Towards improved real-time dual-mode biosensing - Hasler, Roger; Steger-Polt, Marie Helene; Reiner-Rozman, Ciril; Fossati, Stefan; Lee, Seungho; Aspermair, Patrik; Kleber, Christoph; Ibáñez, Maria; Dostalek, Jakub; Knoll, Wolfgang (Frontiers in Physics)
The use of multimodal readout mechanisms next to label-free real-time monitoring of biomolecular interactions can provide valuable insight into surface-based reaction mechanisms. To this end, the combination of an electrolyte-gated field-effect transistor (EG-FET) with a fiber optic-coupled surface plasmon resonance (FO-SPR) probe serving as gate electrode has been investigated to deconvolute surface mass and charge density variations associated to surface reactions. However, applying an electrochemical potential on such gold-coated FO-SPR gate electrodes can induce gradual morphological changes of the thin gold film, leading to an irreversible blue-shift of the SPR wavelength and a substantial signal drift. We show that mild annealing leads to optical and electronic signal stabilization (20-fold lower signal drift than as-sputtered fiber optic gates) and improved overall analytical performance characteristics. The thermal treatment prevents morphological changes of the thin gold-film occurring during operation, hence providing reliable and stable data immediately upon gate voltage application. Thus, the readout output of both transducing principles, the optical FO-SPR and electronic EG-FET, stays constant throughout the whole sensing time-window and the long-term effect of thermal treatment is also improved, providing stable signals even after 1 year of storage. Annealing should therefore be considered a necessary modification for applying fiber optic gate electrodes in real-time multimodal investigations of surface reactions at the solid-liquid interface.

On unsteady internal flows of incompressible fluids characterized by implicit constitutive equations in the bulk and on the boundary - Bulíček, Miroslav; Málek, Josef; Maringová, Erika (Journal of Mathematical Fluid Mechanics)
Long-time and large-data existence of weak solutions for initial- and boundary-value problems concerning three-dimensional flows of incompressible fluids is nowadays available not only for Navier–Stokes fluids but also for various fluid models where the relation between the Cauchy stress tensor and the symmetric part of the velocity gradient is nonlinear. The majority of such studies however concerns models where such a dependence is explicit (the stress is a function of the velocity gradient), which makes the class of studied models unduly restrictive. The same concerns boundary conditions, or more precisely the slipping mechanisms on the boundary, where the no-slip is still the most preferred condition considered in the literature. Our main objective is to develop a robust mathematical theory for unsteady internal flows of implicitly constituted incompressible fluids with implicit relations between the tangential projections of the velocity and the normal traction on the boundary. The theory covers numerous rheological models used in chemistry, biorheology, polymer and food industry as well as in geomechanics. It also includes, as special cases, nonlinear slip as well as stick–slip boundary conditions. Unlike earlier studies, the conditions characterizing admissible classes of constitutive equations are expressed by means of tools of elementary calculus. In addition, a fully constructive proof (approximation scheme) is incorporated. Finally, we focus on the question of uniqueness of such weak solutions.

3D cell segregation geometry and dynamics are governed by tissue surface tension regulation - Méhes, Elod; Mones, Enys; Varga, Máté; Zsigmond, Áron; Biri-Kovács, Beáta; Nyitray, László; Barone, Vanessa; Krens, Gabriel; Heisenberg, Carl-Philipp J; Vicsek, Tamás (Communications Biology)
Tissue morphogenesis and patterning during development involve the segregation of cell types. Segregation is driven by differential tissue surface tensions generated by cell types through controlling cell-cell contact formation by regulating adhesion and actomyosin contractility-based cellular cortical tensions. We use vertebrate tissue cell types and zebrafish germ layer progenitors as in vitro models of 3-dimensional heterotypic segregation and developed a quantitative analysis of their dynamics based on 3D time-lapse microscopy. We show that general inhibition of actomyosin contractility by the Rho kinase inhibitor Y27632 delays segregation. Cell type-specific inhibition of non-muscle myosin2 activity by overexpression of myosin assembly inhibitor S100A4 reduces tissue surface tension, manifested in decreased compaction during aggregation and inverted geometry observed during segregation. The same is observed when we express a constitutively active Rho kinase isoform to ubiquitously keep actomyosin contractility high at cell-cell and cell-medium interfaces and thus overriding the interface-specific regulation of cortical tensions. Tissue surface tension regulation can become an effective tool in tissue engineering.

The membrane surface as a platform that organizes cellular and biochemical processes - Leonard, Thomas A.; Loose, Martin; Martens, Sascha (Developmental Cell)
Membranes are essential for life. They act as semi-permeable boundaries that define cells and organelles. In addition, their surfaces actively participate in biochemical reaction networks, where they confine proteins, align reaction partners, and directly control enzymatic activities. Membrane-localized reactions shape cellular membranes, define the identity of organelles, compartmentalize biochemical processes, and can even be the source of signaling gradients that originate at the plasma membrane and reach into the cytoplasm and nucleus. The membrane surface is, therefore, an essential platform upon which myriad cellular processes are scaffolded. In this review, we summarize our current understanding of the biophysics and biochemistry of membrane-localized reactions with particular focus on insights derived from reconstituted and cellular systems. We discuss how the interplay of cellular factors results in their self-organization, condensation, assembly, and activity, and the emergent properties derived from them.

The Ycf48 accessory factor occupies the site of the oxygen-evolving manganese cluster during photosystem II biogenesis - Zhao, Ziyu; Vercellino, Irene; Knoppová, Jana; Sobotka, Roman; Murray, James W.; Nixon, Peter J.; Sazanov, Leonid A; Komenda, Josef (Nature Communications)
Robust oxygenic photosynthesis requires a suite of accessory factors to ensure efficient assembly and repair of the oxygen-evolving photosystem two (PSII) complex. The highly conserved Ycf48 assembly factor binds to the newly synthesized D1 reaction center polypeptide and promotes the initial steps of PSII assembly, but its binding site is unclear. Here we use cryo-electron microscopy to determine the structure of a cyanobacterial PSII D1/D2 reaction center assembly complex with Ycf48 attached. Ycf48, a 7-bladed beta propeller, binds to the amino-acid residues of D1 that ultimately ligate the water-oxidising Mn4CaO5 cluster, thereby preventing the premature binding of Mn2+ and Ca2+ ions and protecting the site from damage. Interactions with D2 help explain how Ycf48 promotes assembly of the D1/D2 complex. Overall, our work provides valuable insights into the early stages of PSII assembly and the structural changes that create the binding site for the Mn4CaO5 cluster.

Stopping criteria for value iteration on stochastic games with quantitative objectives - Kretinsky, Jan; Meggendorfer, Tobias; Weininger, Maximilian (38th Annual ACM/IEEE Symposium on Logic in Computer Science)
A classic solution technique for Markov decision processes (MDP) and stochastic games (SG) is value iteration (VI). Due to its good practical performance, this approximative approach is typically preferred over exact techniques, even though no practical bounds on the imprecision of the result could be given until recently. As a consequence, even the most used model checkers could return arbitrarily wrong results. Over the past decade, different works derived stopping criteria, indicating when the precision reaches the desired level, for various settings, in particular MDP with reachability, total reward, and mean payoff, and SG with reachability.In this paper, we provide the first stopping criteria for VI on SG with total reward and mean payoff, yielding the first anytime algorithms in these settings. To this end, we provide the solution in two flavours: First through a reduction to the MDP case and second directly on SG. The former is simpler and automatically utilizes any advances on MDP. The latter allows for more local computations, heading towards better practical efficiency.Our solution unifies the previously mentioned approaches for MDP and SG and their underlying ideas. To achieve this, we isolate objective-specific subroutines as well as identify objective-independent concepts. These structural concepts, while surprisingly simple, form the very essence of the unified solution.

Concepts, mechanisms and implications of long-term epigenetic inheritance - Hollwey, Elizabeth; Briffa, Amy; Howard, Martin; Zilberman, Daniel (Current Opinion in Genetics and Development)
Many modes and mechanisms of epigenetic inheritance have been elucidated in eukaryotes. Most of them are relatively short-term, generally not exceeding one or a few organismal generations. However, emerging evidence indicates that one mechanism, cytosine DNA methylation, can mediate epigenetic inheritance over much longer timescales, which are mostly or completely inaccessible in the laboratory. Here we discuss the evidence for, and mechanisms and implications of, such long-term epigenetic inheritance. We argue that compelling evidence supports the long-term epigenetic inheritance of gene body methylation, at least in the model angiosperm Arabidopsis thaliana, and that variation in such methylation can therefore serve as an epigenetic basis for phenotypic variation in natural populations.

The molecular basis of sexual dimorphism: Experimental and theoretical characterization of phenotypic, transcriptomic and genetic patterns of sex-specific adaptation - Puixeu Sala, Gemma
Females and males across species are subject to divergent selective pressures arising from di↵erent reproductive interests and ecological niches. This often translates into a intricate array of sex-specific natural and sexual selection on traits that have a shared genetic basis between both sexes, causing a genetic sexual conflict. The resolution of this conflict mostly relies on the evolution of sex-specific expression of the shared genes, leading to phenotypic sexual dimorphism. Such sex-specific gene expression is thought to evolve via modifications of the genetic networks ultimately linked to sex-determining transcription factors. Although much empirical and theoretical evidence supports this standard picture of the molecular basis of sexual conflict resolution, there still are a few open questions regarding the complex array of selective forces driving phenotypic di↵erentiation between the sexes, as well as the molecular mechanisms underlying sexspecific adaptation. I address some of these open questions in my PhD thesis. First, how do patterns of phenotypic sexual dimorphism vary within populations, as a response to the temporal and spatial changes in sex-specific selective forces? To tackle this question, I analyze the patterns of sex-specific phenotypic variation along three life stages and across populations spanning the whole geographical range of Rumex hastatulus, a wind-pollinated angiosperm, in the first Chapter of the thesis. Second, how do gene expression patterns lead to phenotypic dimorphism, and what are the molecular mechanisms underlying the observed transcriptomic variation? I address this question by examining the sex- and tissue-specific expression variation in newly-generated datasets of sex-specific expression in heads and gonads of Drosophila melanogaster. I additionally used two complementary approaches for the study of the genetic basis of sex di↵erences in gene expression in the second and third Chapters of the thesis. Third, how does intersex correlation, thought to be one of the main aspects constraining the ability for the two sexes to decouple, interact with the evolution of sexual dimorphism? I develop models of sex-specific stabilizing selection, mutation and drift to formalize common intuition regarding the patterns of covariation between intersex correlation and sexual dimorphism in the fourth Chapter of the thesis. Alltogether, the work described in this PhD thesis provides useful insights into the links between genetic, transcriptomic and phenotypic layers of sex-specific variation, and contributes to our general understanding of the dynamics of sexual dimorphism evolution.

Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster - Puixeu Sala, Gemma; Macon, Ariana; Vicoso, Beatriz (G3: Genes, Genomes, Genetics)
The regulatory architecture of gene expression is known to differ substantially between sexes in Drosophila, but most studies performed so far used whole-body data and only single crosses, which may have limited their scope to detect patterns that are robust across tissues and biological replicates. Here, we use allele-specific gene expression of parental and reciprocal hybrid crosses between 6 Drosophila melanogaster inbred lines to quantify cis- and trans-regulatory variation in heads and gonads of both sexes separately across 3 replicate crosses. Our results suggest that female and male heads, as well as ovaries, have a similar regulatory architecture. On the other hand, testes display more and substantially different cis-regulatory effects, suggesting that sex differences in the regulatory architecture that have been previously observed may largely derive from testis-specific effects. We also examine the difference in cis-regulatory variation of genes across different levels of sex bias in gonads and heads. Consistent with the idea that intersex correlations constrain expression and can lead to sexual antagonism, we find more cis variation in unbiased and moderately biased genes in heads. In ovaries, reduced cis variation is observed for male-biased genes, suggesting that cis variants acting on these genes in males do not lead to changes in ovary expression. Finally, we examine the dominance patterns of gene expression and find that sex- and tissue-specific patterns of inheritance as well as trans-regulatory variation are highly variable across biological crosses, although these were performed in highly controlled experimental conditions. This highlights the importance of using various genetic backgrounds to infer generalizable patterns.
Keywords: Genetics (clinical); Genetics; Molecular Biology

ZnUMBA - a live imaging method to detect local barrier breaches - Higashi, Tomohito; Stephenson, Rachel E.; Schwayer, Cornelia; Huljev, Karla; Higashi, Atsuko Y.; Heisenberg, Carl-Philipp J; Chiba, Hideki; Miller, Ann L. (Journal of Cell Science)
Epithelial barrier function is commonly analyzed using transepithelial electrical resistance, which measures ion flux across a monolayer, or by adding traceable macromolecules and monitoring their passage across the monolayer. Although these methods measure changes in global barrier function, they lack the sensitivity needed to detect local or transient barrier breaches, and they do not reveal the location of barrier leaks. Therefore, we previously developed a method that we named the zinc-based ultrasensitive microscopic barrier assay (ZnUMBA), which overcomes these limitations, allowing for detection of local tight junction leaks with high spatiotemporal resolution. Here, we present expanded applications for ZnUMBA. ZnUMBA can be used in Xenopus embryos to measure the dynamics of barrier restoration and actin accumulation following laser injury. ZnUMBA can also be effectively utilized in developing zebrafish embryos as well as cultured monolayers of Madin–Darby canine kidney (MDCK) II epithelial cells. ZnUMBA is a powerful and flexible method that, with minimal optimization, can be applied to multiple systems to measure dynamic changes in barrier function with spatiotemporal precision.

Practical limitations of Ethereum’s layer-2 - Neiheiser, Ray; Inacio, Gustavo; Rech, Luciana; Montez, Carlos; Matos, Miguel; Rodrigues, Luis (IEEE Access)
Most permissionless blockchains inherently suffer from throughput limitations. Layer-2 systems, such as side-chains or Rollups, have been proposed as a possible strategy to overcome this limitation. Layer-2 systems interact with the main-chain in two ways. First, users can move funds from/to the main-chain to/from the layer-2. Second, layer-2 systems periodically synchronize with the main-chain to keep some form of log of their activity on the main-chain - this log is key for security. Due to this interaction with the main-chain, which is necessary and recurrent, layer-2 systems impose some load on the main-chain. The impact of such load on the main-chain has been, so far, poorly understood. In addition to that, layer-2 approaches typically sacrifice decentralization and security in favor of higher throughput. This paper presents an experimental study that analyzes the current state of Ethereum layer-2 projects. Our goal is to assess the load they impose on Ethereum and to understand their scalability potential in the long-run. Our analysis shows that the impact of any given layer-2 on the main-chain is the result of both technical aspects (how state is logged on the main-chain) and user behavior (how often users decide to transfer funds between the layer-2 and the main-chain). Based on our observations, we infer that without efficient mechanisms that allow users to transfer funds in a secure and fast manner directly from one layer-2 project to another, current layer-2 systems will not be able to scale Ethereum effectively, regardless of their technical solutions. Furthermore, from our results, we conclude that the layer-2 systems that offer similar security guarantees as Ethereum have limited scalability potential, while approaches that offer better performance, sacrifice security and lead to an increase in centralization which runs against the end-goals of permissionless blockchains.
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Data from: Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster - Puixeu Sala, Gemma
Datasets of the publication "Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster".

Horospherical coordinates of lattice points in hyperbolic spaces: Effective counting and equidistribution - Horesh, Tal; Nevo, Amos (Pacific Journal of Mathematics)
We establish effective counting results for lattice points in families of domains in real, complex and quaternionic hyperbolic spaces of any dimension. The domains we focus on are defined as product sets with respect to an Iwasawa decomposition. Several natural diophantine problems can be reduced to counting lattice points in such domains. These include equidistribution of the ratio of the length of the shortest solution (x,y) to the gcd equation bx−ay=1 relative to the length of (a,b), where (a,b) ranges over primitive vectors in a disc whose radius increases, the natural analog of this problem in imaginary quadratic number fields, as well as equidistribution of integral solutions to the diophantine equation defined by an integral Lorentz form in three or more variables. We establish an effective rate of convergence for these equidistribution problems, depending on the size of the spectral gap associated with a suitable lattice subgroup in the isometry group of the relevant hyperbolic space. The main result underlying our discussion amounts to establishing effective joint equidistribution for the horospherical component and the radial component in the Iwasawa decomposition of lattice elements.

Emergence of a Bose polaron in a small ring threaded by the Aharonov-Bohm flux - Brauneis, Fabian; Ghazaryan, Areg; Hammer, Hans-Werner; Volosniev, Artem (Communications Physics)
The model of a ring threaded by the Aharonov-Bohm flux underlies our understanding of a coupling between gauge potentials and matter. The typical formulation of the model is based upon a single particle picture, and should be extended when interactions with other particles become relevant. Here, we illustrate such an extension for a particle in an Aharonov-Bohm ring subject to interactions with a weakly interacting Bose gas. We show that the ground state of the system can be described using the Bose-polaron concept—a particle dressed by interactions with a bosonic environment. We connect the energy spectrum to the effective mass of the polaron, and demonstrate how to change currents in the system by tuning boson-particle interactions. Our results suggest the Aharonov-Bohm ring as a platform for studying coherence and few- to many-body crossover of quasi-particles that arise from an impurity immersed in a medium.
Keywords: General Physics and Astronomy

Homological Bondal-Orlov localization conjecture for rational singularities - Mauri, Mirko; Shinder, Evgeny (Forum of Mathematics, Sigma)
Given a resolution of rational singularities π:X~→X over a field of characteristic zero, we use a Hodge-theoretic argument to prove that the image of the functor Rπ∗:Db(X~)→Db(X) between bounded derived categories of coherent sheaves generates Db(X) as a triangulated category. This gives a weak version of the Bondal–Orlov localization conjecture [BO02], answering a question from [PS21]. The same result is established more generally for proper (not necessarily birational) morphisms π:X~→X , with X~ smooth, satisfying Rπ∗(OX~)=OX .

On the global minimum of the energy–momentum relation for the polaron - Lampart, Jonas; Mitrouskas, David Johannes; Mysliwy, Krzysztof (Mathematical Physics, Analysis and Geometry)
For the Fröhlich model of the large polaron, we prove that the ground state energy as a function of the total momentum has a unique global minimum at momentum zero. This implies the non-existence of a ground state of the translation invariant Fröhlich Hamiltonian and thus excludes the possibility of a localization transition at finite coupling.
Keywords: Geometry and Topology; Mathematical Physics

Nonadiabatic laser-induced alignment dynamics of molecules on a surface - Kranabetter, Lorenz; Kristensen, Henrik H.; Ghazaryan, Areg; Schouder, Constant A.; Chatterley, Adam S.; Janssen, Paul; Jensen, Frank; Zillich, Robert E.; Lemeshko, Mikhail; Stapelfeldt, Henrik (Physical Review Letters)
We demonstrate that a sodium dimer, Na2(13Σ+u), residing on the surface of a helium nanodroplet, can be set into rotation by a nonresonant 1.0 ps infrared laser pulse. The time-dependent degree of alignment measured, exhibits a periodic, gradually decreasing structure that deviates qualitatively from that expected for gas-phase dimers. Comparison to alignment dynamics calculated from the time-dependent rotational Schrödinger equation shows that the deviation is due to the alignment dependent interaction between the dimer and the droplet surface. This interaction confines the dimer to the tangential plane of the droplet surface at the point where it resides and is the reason that the observed alignment dynamics is also well described by a 2D quantum rotor model.

The phenuivirus Toscana virus makes an atypical use of vacuolar acidity to enter host cells - Koch, Jana; Xin, Qilin; Obr, Martin; Schäfer, Alicia; Rolfs, Nina; Anagho, Holda A.; Kudulyte, Aiste; Woltereck, Lea; Kummer, Susann; Campos, Joaquin; Uckeley, Zina M.; Bell-Sakyi, Lesley; et al. (PLoS Pathogens)
Toscana virus is a major cause of arboviral disease in humans in the Mediterranean basin during summer. However, early virus-host cell interactions and entry mechanisms remain poorly characterized. Investigating iPSC-derived human neurons and cell lines, we found that virus binding to the cell surface was specific, and 50% of bound virions were endocytosed within 10 min. Virions entered Rab5a+ early endosomes and, subsequently, Rab7a+ and LAMP-1+ late endosomal compartments. Penetration required intact late endosomes and occurred within 30 min following internalization. Virus entry relied on vacuolar acidification, with an optimal pH for viral membrane fusion at pH 5.5. The pH threshold increased to 5.8 with longer pre-exposure of virions to the slightly acidic pH in early endosomes. Strikingly, the particles remained infectious after entering late endosomes with a pH below the fusion threshold. Overall, our study establishes Toscana virus as a late-penetrating virus and reveals an atypical use of vacuolar acidity by this virus to enter host cells.

Antigravitropic PIN polarization maintains non-vertical growth in lateral roots - Roychoudhry, S; Sageman-Furnas, K; Wolverton, C; Grones, Peter; Tan, Shutang; Molnar, Gergely; De Angelis, M; Goodman, HL; Capstaff, N; JPB, Lloyd; Mullen, J; Hangarter, R; et al. (Nature Plants)
Lateral roots are typically maintained at non-vertical angles with respect to gravity. These gravitropic setpoint angles are intriguing because their maintenance requires that roots are able to effect growth response both with and against the gravity vector, a phenomenon previously attributed to gravitropism acting against an antigravitropic offset mechanism. Here we show how the components mediating gravitropism in the vertical primary root—PINs and phosphatases acting upon them—are reconfigured in their regulation such that lateral root growth at a range of angles can be maintained. We show that the ability of Arabidopsis lateral roots to bend both downward and upward requires the generation of auxin asymmetries and is driven by angle-dependent variation in downward gravitropic auxin flux acting against angle-independent upward, antigravitropic flux. Further, we demonstrate a symmetry in auxin distribution in lateral roots at gravitropic setpoint angle that can be traced back to a net, balanced polarization of PIN3 and PIN7 auxin transporters in the columella. These auxin fluxes are shifted by altering PIN protein phosphoregulation in the columella, either by introducing PIN3 phosphovariant versions or via manipulation of levels of the phosphatase subunit PP2A/RCN1. Finally, we show that auxin, in addition to driving lateral root directional growth, acts within the lateral root columella to induce more vertical growth by increasing RCN1 levels, causing a downward shift in PIN3 localization, thereby diminishing the magnitude of the upward, antigravitropic auxin flux.

Mitochondrial network adaptations of microglia reveal sex-specific stress response after injury and UCP2 knockout - Maes, Margaret E; Colombo, Gloria; Schoot Uiterkamp, Florianne E; Sternberg, Felix; Venturino, Alessandro; Pohl, Elena E.; Siegert, Sandra (iScience)
Mitochondrial networks remodel their connectivity, content, and subcellular localization to support optimized energy production in conditions of increased environmental or cellular stress. Microglia rely on mitochondria to respond to these stressors, however our knowledge about mitochondrial networks and their adaptations in microglia in vivo is limited. Here, we generate a mouse model that selectively labels mitochondria in microglia. We identify that mitochondrial networks are more fragmented with increased content and perinuclear localization in vitro vs. in vivo. Mitochondrial networks adapt similarly in microglia closest to the injury site after optic nerve crush. Preventing microglial UCP2 increase after injury by selective knockout induces cellular stress. This results in mitochondrial hyperfusion in male microglia, a phenotype absent in females due to circulating estrogens. Our results establish the foundation for mitochondrial network analysis of microglia in vivo, emphasizing the importance of mitochondrial-based sex effects of microglia in other pathologies.

Gaussian fluctuations in the equipartition principle for Wigner matrices - Cipolloni, Giorgio; Erdös, László; Henheik, Sven Joscha; Kolupaiev, Oleksii (Forum of Mathematics, Sigma)
The total energy of an eigenstate in a composite quantum system tends to be distributed equally among its constituents. We identify the quantum fluctuation around this equipartition principle in the simplest disordered quantum system consisting of linear combinations of Wigner matrices. As our main ingredient, we prove the Eigenstate Thermalisation Hypothesis and Gaussian fluctuation for general quadratic forms of the bulk eigenvectors of Wigner matrices with an arbitrary deformation.

Why extension-based proofs fail - Alistarh, Dan-Adrian; Aspnes, James; Ellen, Faith; Gelashvili, Rati; Zhu, Leqi (SIAM Journal on Computing)
We introduce extension-based proofs, a class of impossibility proofs that includes valency arguments. They are modelled as an interaction between a prover and a protocol. Using proofs based on combinatorial topology, it has been shown that it is impossible to deterministically solve -set agreement among processes or approximate agreement on a cycle of length 4 among processes in a wait-free manner in asynchronous models where processes communicate using objects that can be constructed from shared registers. However, it was unknown whether proofs based on simpler techniques were possible. We show that these impossibility results cannot be obtained by extension-based proofs in the iterated snapshot model and, hence, extension-based proofs are limited in power.

On angles in higher order Brillouin tessellations and related tilings in the plane - Edelsbrunner, Herbert; Garber, Alexey; Ghafari, Mohadese; Heiss, Teresa; Saghafian, Morteza (Discrete and Computational Geometry)
For a locally finite set in R2, the order-k Brillouin tessellations form an infinite sequence of convex face-to-face tilings of the plane. If the set is coarsely dense and generic, then the corresponding infinite sequences of minimum and maximum angles are both monotonic in k. As an example, a stationary Poisson point process in R2 is locally finite, coarsely dense, and generic with probability one. For such a set, the distributions of angles in the Voronoi tessellations, Delaunay mosaics, and Brillouin tessellations are independent of the order and can be derived from the formula for angles in order-1 Delaunay mosaics given by Miles (Math. Biosci. 6, 85–127 (1970)).

Self-organized and directed branching results in optimal coverage in developing dermal lymphatic networks - Ucar, Mehmet C; Hannezo, Edouard B; Tiilikainen, Emmi; Liaqat, Inam; Jakobsson, Emma; Nurmi, Harri; Vaahtomeri, Kari (Nature Communications)
Branching morphogenesis is a ubiquitous process that gives rise to high exchange surfaces in the vasculature and epithelial organs. Lymphatic capillaries form branched networks, which play a key role in the circulation of tissue fluid and immune cells. Although mouse models and correlative patient data indicate that the lymphatic capillary density directly correlates with functional output, i.e., tissue fluid drainage and trafficking efficiency of dendritic cells, the mechanisms ensuring efficient tissue coverage remain poorly understood. Here, we use the mouse ear pinna lymphatic vessel network as a model system and combine lineage-tracing, genetic perturbations, whole-organ reconstructions and theoretical modeling to show that the dermal lymphatic capillaries tile space in an optimal, space-filling manner. This coverage is achieved by two complementary mechanisms: initial tissue invasion provides a non-optimal global scaffold via self-organized branching morphogenesis, while VEGF-C dependent side-branching from existing capillaries rapidly optimizes local coverage by directionally targeting low-density regions. With these two ingredients, we show that a minimal biophysical model can reproduce quantitatively whole-network reconstructions, across development and perturbations. Our results show that lymphatic capillary networks can exploit local self-organizing mechanisms to achieve tissue-scale optimization.

Synchronization in collectively moving inanimate and living active matter - Riedl, Michael; Mayer, Isabelle D; Merrin, Jack; Sixt, Michael K; Hof, Björn (Nature Communications)
Whether one considers swarming insects, flocking birds, or bacterial colonies, collective motion arises from the coordination of individuals and entails the adjustment of their respective velocities. In particular, in close confinements, such as those encountered by dense cell populations during development or regeneration, collective migration can only arise coordinately. Yet, how individuals unify their velocities is often not understood. Focusing on a finite number of cells in circular confinements, we identify waves of polymerizing actin that function as a pacemaker governing the speed of individual cells. We show that the onset of collective motion coincides with the synchronization of the wave nucleation frequencies across the population. Employing a simpler and more readily accessible mechanical model system of active spheres, we identify the synchronization of the individuals’ internal oscillators as one of the essential requirements to reach the corresponding collective state. The mechanical ‘toy’ experiment illustrates that the global synchronous state is achieved by nearest neighbor coupling. We suggest by analogy that local coupling and the synchronization of actin waves are essential for the emergent, self-organized motion of cell collectives.